Fungal Extracellular Vesicles are Recoverable Across Variable Ultracentrifugation Speeds but Display Species-specific Profiles of Sedimentation - Luisa J. Jozefowicz; Bárbara T. Bezerra; Eva Veres; Zóra Szilovics; Cássia M. Souza; Amanda C. Camillo-Andrade; Hellen G. G. Santos; Paulo C. Carvalho; Marlon D. M. Santos; Flavia C. G. Reis; Attila Gacser; Marcio L. Rodrigues (The Journal of Membrane Biology, 2026)

The COVID-19 pandemic influenced the temporal dynamics of antimicrobial resistance markers and bacterial community across urban wastewater treatment plants - Celso G. B. Filho; Francisca A. S. Oliveira; Victor L. M. Rodrigues; Denise C. Hissa; Maisa V. H. Barros; Allysson A. de Farias; Gabriel T. Dantas; André B. dos Santos; Julio C. M. Ximenes; Vânia M. M. Melo (Brazilian Journal of Microbiology, 2026)
Urban wastewater systems represent important interfaces between human activity and the environmental occurrence of antimicrobial resistance (AMR) markers. We assessed the temporal dynamics of intI1 , ermB , and the 16 S rRNA gene by quantitative PCR across three wastewater systems (EPC, CJC, and JW) in Fortaleza, Brazil, from November 2021 to November 2023. Bacterial communities were additionally characterized by 16 S rRNA gene metabarcoding in 18 samples collected in December 2021 and January 2022. A synchronized decline in 16 S rRNA gene and intI1 concentrations beginning in late 2022 was observed across all three wastewater systems, suggesting a shift toward lower microbial abundance. The ermB gene showed higher and more variable concentrations during part of the pandemic period, followed by convergence toward lower levels; however, the absence of antimicrobial-consumption data precluded attribution of this pattern to changes in macrolide selective pressure. Normalized antimicrobial resistance marker abundances were comparatively stable at EPC and JW but more variable at CJC. EPC exhibited the highest ASV richness, whereas CJC and JW showed greater diversity according to Shannon and inverse Simpson indices. Beta-diversity analyses identified wastewater system as the principal factor associated with bacterial community structure, while the effect of sampling period was smaller and metric-dependent. Neither ermB nor intI1 was individually associated with community composition, although intI1 showed a limited effect after adjustment for wastewater system in one model. Physicochemical parameters were not significantly associated with normalized marker abundances in the exploratory paired analysis. Arcobacter , Acinetobacter , and other potentially relevant genera were detected, but no direct associations between these taxa and the monitored AMR markers could be established. These findings highlight the value of integrating longitudinal qPCR, microbiome profiling, and environmental characterization to improve the interpretation of targeted AMR markers in One Health wastewater surveillance.

Mode choice during transport disruptions: Socioeconomic and trip factors in shared mobility adoption in the Netherlands - Luiza Gagno Azolin; Antônio Nélson Rodrigues da Silva; Luqi Dong; Anna Beatriz Grigolon; Karst T. Geurs (Travel Behaviour and Society, 2026)

Bioinspired pullulan-based adhesive coacervate films for targeted buccal delivery of peptides - Margarida M.A. Sacramento; Nazanin Z. Ezazi; Eleftheria Pantazoglou; Philip Mark Lund; Marco van de Weert; Zhongyang Zhang; Rui Vitorino; Floriane Bahuon; Ragna Berthelsen; Stephen T. Buckley; Gavrielle R. Untracht; Peter Eskil Andersen; et al. (Carbohydrate Polymers, 2026)

Dietary supplementation with algae-based ingredients modulates antioxidant defenses and immune response in sea urchin Paracentrotus lividus following a Vibrio parahaemolyticus challenge - Ana Filipa Rodrigues; S. Lourenço; A.S. Gomes; M. Vaz; H. Cardoso; A.P. Violante; T. Baptista (Animal Feed Science and Technology, 2026)

Benthic scavenger assemblages along a depth gradient: megafauna–macrofauna divergence - Diego Carreira-Flores; Filipa Rodrigues; Pedro T. Gomes; Marcos Rubal (Marine Environmental Research, 2026)

Texturally targeted multi-isotopic dating of ductile deformation: the Clarke River Shear Zone, northeastern Australia - Raiza T. Rodrigues; Bruno V. Ribeiro; Gideon Rosenbaum; Fred Jourdan; Teresa Ubide; Kai Rankenburg (Journal of Structural Geology, 2026)

Promoter Engineering of the Surfactin Operon Enhances Surfactin Production in the Environmental Strain Bacillus subtilis RI4914 - Michelle Fernandes Almeida; Fernanda de Souza Freitas; Bruna Almeida Leão Ayupe; Janine T. Bossé; Denise Mara Soares Bazzolli; Victor Satler Pylro; Pedro Marcus Pereira Vidigal; Humberto Josué de Oliveira Ramos; Edmo Montes Rodrigues; Marcos Rogério Tótola (Current Microbiology, 2026)
This study aimed to enhance surfactin production in Bacillus subtilis by replacing the native promoter of the surfactin synthase operon (P srfA ) with the strong IPTG-inducible promoter Pgrac to address challenges in large-scale biosurfactant production. The engineered strain was developed through homologous recombination, creating an integration cassette fused via overlap extension PCR and transformed into B. subtilis RI4914. Surfactin yields were assessed via oil spreading and UPLC-MS. Results showed that surfactin synthesis in the modified strain was nearly absent without IPTG. With IPTG, however, production surged 8.4-fold compared to the wild type, reaching 4.8 g/L. Productivity and carbon source yield also improved 8-fold and 11-fold, respectively. This promoter engineering strategy significantly enhanced surfactin production, with the observed increase being consistent with the expected behavior of IPTG-inducible Pgrac systems in Bacillus subtilis, suggesting an effective regulatory response associated with the tested expression system.

Anti-inflammatory potential of the CISACN adduct in LPS-induced murine models - Louise M. de Lima; Francisco A. A. F. Gadelha; Laércia K. D. Paiva Ferreira; Cosmo I. D. Vieira; João B. de Oliveira; Larissa A. M. Paiva Ferreira; Matheus Victor de Souza Laurentino; Bruno Vinícius da Silva Moura; Teresa Carolliny M. L. Rodrigues; Tayná R. Olegário; Luciana Scotti; Marcus T. Scotti; et al. (Inflammopharmacology, 2026)

The Role of Gene Flow in the Diversification of the Monkey Treefrog Complex Across the South American Dry Diagonal - Felipe Camurugi; Vinícius A. São Pedro; Felipe Magalhães; Marcelo Gehara; Eliana F. Oliveira; Gabriel C. Costa; Frank T. Burbrink; Edward A. Myers; Guarino R. Colli; Miguel T. Rodrigues; Adrian A. Garda (Zoologica Scripta, 2026)
Understanding Neotropical megadiversity remains challenging due to fundamental taxonomic issues, including identifying and describing cryptic species and their distribution, and the limited knowledge of key factors driving biological diversification. Such challenges are especially prominent in diverse clades with high levels of cryptic species, such as many Neotropical frogs. Herein, we conduct a mitochondrial phylogenetic study on monkey treefrogs in the genus Pithecopus and a multilocus analysis of the P. hypochondrialis species group throughout its distribution in the South American dry diagonal (DD). Our goals were to infer the main lineages and identify historical factors that led to their divergence. Among nine currently recognised species, we found 14 well‐structured mitochondrial lineages in two main clades, which diversified during the Paleogene/Neogene transition. The lowland clade is widely distributed in the DD, and our multilocus analysis suggests it comprises seven geographically structured lineages: P. azureus , two lineages of P. hypochondrialis , two species and one lineage for the P. nordestinus complex, and Pithecopus sp. Considering the geomorphological history of the region, diversification may have been promoted by allopatric speciation during Miocene paleogeographic events, especially the Brazilian Plateau compartmentalization and fluctuations in the São Francisco River water volume. Furthermore, gene flow between some lineages may be explained by niche conservatism and demographic expansions during the late Pleistocene, a period marked by climatic fluctuations and biome shifts. Our results reinforce the importance of both Neogene tectonic activity and Quaternary climatic fluctuations in shaping the Neotropical biota.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Monte San Nicola (Sicily): Gelasian GSSP and base Quaternary/Pleistocene - L. Capraro; S. Bonomo; A. Incarbona; F.J. Hilgen; E. Zanola; A. Di Stefano; F. Dela Pierre; S. Ferraro; P. Ferretti; E. Fornaciari; S. Galeotti; P. Macrì; et al. (Quaternary Science Reviews, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Inverse Bayesian Estimation of Time-Varying Pollutant Loads at River Margins - Bruno C. Lugão; Diego C. Knupp; Leonardo T. Stutz; Pedro Paulo G. W. Rodrigues (Environmental Modeling & Assessment, 2026)

American Useful Plants in Post-Medieval Europe: Integrating Archaeobotanical and Historical Evidence - J. Irmišová; M. Ballesteros; J. J. Garay-Vázquez; C. Moricca; J. Skružná; T. Majerovičová; L. Speleers; S. Preiss; M. Badura; J. Wiethold; O. Brinkkemper; J. P. V. Tereso; et al. (Ethnobotany and Economic Botany, 2026)
The arrival of Europeans in the Americas in 1492 initiated new transatlantic connections that, through colonial expansion and trade networks, brought useful plants to Europe. This study investigates archaeobotanical and historical evidence for the introduction of American plants to Europe from the late fifteenth to the twentieth century. We compiled 183 archaeobotanical records from 14 countries, representing 24 taxa from 11 botanical families. We examined which American plant species were introduced to Europe during the post-medieval period, and how their uses and significance varied across regions and social contexts. Archaeobotanical data indicate that early introductions occurred predominantly in elite secular and ecclesiastical settings across Europe. Historical sources identify Spain as the first entry point, though other European countries yielded more records. The large number of archaeobotanical finds in the Netherlands and at the Habsburg court in Prague reflects the current state of research, site coverage, preservation, and data accessibility. The significance of these plants in Europe was shaped by economic value, prestige, ritual use, and medicinal properties. Our study highlights the importance of integrating archaeobotanical and historical sources and provides the most comprehensive account to date of material evidence tracing the cultural trajectories of American plants in Europe.

Targeting hypertension through natural phenolics: The multifaceted role of cinnamic acid and its derivatives - Samuel S. P. de Araujo; Brenda L. B. dos Santos; Waldilleny R. A. de Moura; Leonardo G. Rodrigues; Luiz G. S. Branco; Helio C. Salgado; Renato N. Soriano; Marina de T. Durand; João Paulo J. Sabino (Pflügers Archiv - European Journal of Physiology, 2026)

Quantification and characterization of collagen in experimentally induced wounds treated with different types of platelet-rich plasma gel - G. Haro de Melo; F. M. Moreira; G. G. Mori; L. F. Bento; D. V. Barrionuevo; C. B. Laposy; R. Giuffrida; A. F. F. Rodrigues; G. A. T. Ozaki; D. A. F. da Silva; F. L. Pacagnelli; R. M. B. Nogueira (Cell and Tissue Banking, 2026)
Due to its high concentration of growth factors, platelet-rich plasma (PRP) has become the subject of much research, either as an isolated or adjuvant treatment for wound repair. The fractal dimension has been used as an innovative method for the characterization and quantification of tissue structural alterations without any interference from the evaluator. The objective of this study was characterizing collagen types I and III in experimentally induced wounds and treated with different PRP sources by means of fractal dimension and other histological analyzes using blades stained with picrocirius-red and hematoxylin-eosin (HE). In statistical analysis, the variables presented a non-parametric distribution; thus, Mann-Whitney and Kruskall-Wallis tests ( p < 0,05) were performed using the Student-Newman-Keuls method. It was observed an increase of the collagen fibers by measuring the area with Threshold Color in the different treatments, especially with autologous PRP ( p = 0.009) and heterologous PRP ( p = 0.016). The fractal dimension of type I collagen had a significant increase for the autologous group ( p = 0.028) in relation to the control, but, on average ( p < 0.05), type III collagen was higher than type I. Fractal dimension was efficient to separately characterize type I and type III collagen fibers. In this study, collagenization was higher in autologous when compared to heterologous and homologous PRP treatments.

Connectivity and Age of Restored Atlantic Forest Fragments Drives Composition and Functionality of the Fungal Community in the Leaf Litter Layer - Guilherme Lucio Martins; Dina in 't Zandt; Luis Fernando Merloti; Wanderlei Bieluczyk; Gabriel Silvestre Rocha; Robert Timmers; Ricardo Ribeiro Rodrigues; Siu Mui Tsai; Wim H. van der Putten (Molecular Ecology, 2026)
The restoration of biodiversity and functional tropical forests is critical to mitigating global biodiversity losses. Aboveground, increasing the connectivity of regenerating forest fragments facilitates the recolonization of tropical forest biodiversity. However, restoring functional ecosystems also requires the recovery of decomposition processes as these are essential in shaping aboveground biodiversity. Therefore, we investigate the role of forest connectivity in restoring the composition and functioning of fungal communities in the leaf litter layer during a chronosequence of forest restoration. In the Brazilian Atlantic Forest, we studied secondary forests regrown between 18 and 55 years after deforestation and different levels of forest connectivity and compared their litter to recently abandoned pastures and undisturbed primary forests. We quantified how forest age and connectivity between fragments influenced the litter fungi composition in relation to tree diversity, litter chemistry and litter isotopes. We show that fungal composition was highly heterogeneous in forest litter, whereas pasture litter exhibited a more homogeneous community. Moreover, forest connectivity had stronger effects on litter fungal composition compared to forest age. Connectivity promoted wood saprotrophs and endophytes, while suppressing soil saprotrophs, with its effects being more evident during later stages of restoration. Fungal guilds such as endophytes and saprophytes were primarily influenced by tree diversity and leaf litter chemistry. We conclude that forest connectivity promotes the re‐establishment of saprophytic fungi capable of decomposing recalcitrant litter substrates, driven mainly by enhancing tree diversity and litter quality. Practical implications of increasing connectivity may relate to forest resilience in front of future climate change scenarios.

Clarifying space use concepts in ecology: Range vs. occurrence distributions - Jesse M. Alston; Christen H. Fleming; Michael J. Noonan; Marlee A. Tucker; Inês Silva; Cody Folta; Thomas S. B. Akre; Abdullahi H. Ali; Jerrold L. Belant; Dean Beyer; Niels Blaum; Katrin Böhning‐Gaese; et al. (Ecology, 2026)
Quantifying animal movements is necessary for answering a wide array of research questions in ecology and conservation biology. Consequently, ecologists have made considerable efforts to identify the best way to estimate an animal's home range, and many methods of estimating home ranges have arisen over the past half a century. Most of these methods fall into two distinct categories of estimators that have only recently been described in statistical detail: those that measure range distributions (methods such as kernel density estimation that quantify the long‐run behavior of a movement process that features restricted space use) and those that measure occurrence distributions (methods such as Brownian bridge movement models and the Correlated Random Walk Library that quantify uncertainty in an animal movement path during a specific period of observation). In this paper, we use theory, simulations, and empirical analysis to demonstrate the importance of appropriately using these two categories of distributions and their estimators. Conflating range and occurrence distributions can have serious consequences for ecological inference and conservation practice. For example, in most situations, home ranges estimated using estimators of occurrence distributions are too small, and this problem is exacerbated by ongoing improvements in tracking technology that enable more frequent and more accurate data on animal movements. We encourage researchers to use estimators of range distributions to quantify home ranges and estimators of occurrence distributions to answer other questions in movement ecology, such as when and where an animal crossed a linear feature, visited a location of interest, or interacted with other animals.

Reply to Discussion by R. A. Henderson of ‘Kinematics of the Clarke River Shear Zone (northeastern Australia) and implications for the tectonic evolution of the Tasmanides’ - R. T. Rodrigues; G. Rosenbaum (Australian Journal of Earth Sciences, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Encapsulation of jabuticaba (Plinia cauliflora) peel extract with whey or pea protein in combination with gum arabic enhances anthocyanin bioaccessibility and metabolite production - Larissa Lorrane Rodrigues Borges; Valdeir Viana Freitas; Janaina Gonçalves Fernandes; Amanda Lais Alves Almeida Nascimento; Hélia de Barros Kobi; Evandro Martins; Pedro Henrique Campelo Felix; Stephen T. Talcottt; Paulo César Stringheta (Food Chemistry, 2026)

Incorporating statistical uncertainty into metamodel-driven Performance-Based Risk Optimization for seismic design - Isabela D. Rodrigues; Seymour M.J. Spence; André T. Beck (Engineering Structures, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Multifunctional glycerol-derived porous carbons bearing C-P(O)- and/or C-S-bonded functionalities: Nanoarchitectonics and application potential through a novel H3PO4-driven route - Paulo H.L. Pinheiro; Robson M. da Silva; Claudio T. Carvalho; Magno A.G. Trindade; Wagner A. Carvalho; Gabriela T.M. Xavier; Raphael Rodrigues (Biomass and Bioenergy, 2026)

Protected areas influence fire regimes globally - A. Cardil; M. Rodrigues; D. Ascoli; M. Ortega; T. Quiñones; M. Erdozain; I. Oliveras Menor; G.L. Spadoni; J. Ramírez; J.R. Molina; F. Mouillot; C.A. Silva; et al. (Journal of Environmental Management, 2026)

Citral impairs intestinal changes caused by ulcerative colitis through modulation of antioxidant, anti-inflammatory and healing activities - Maycon T. Emílio-Silva; Vinícius P. Rodrigues; Antonio J. Ruiz-Malagon; Isabela G. Guidolin; Felipe L. Dario; Mariana M. Fioravanti; Alba Rodriguez-Nogales; Julio Gálvez; Clelia A. Hiruma-Lima (Inflammopharmacology, 2026)

Waterfowl Move Less in Heterogeneous and Human‐Populated Landscapes, With Implications for Spread of Avian Influenza Viruses - Claire S. Teitelbaum; Diann J. Prosser; Joshua T. Ackerman; Sakib Ahmed; A. B. M. Sarowar Alam; Kazi Zenifar Azmiri; Nyambaya Batbayar; Joël Bêty; Abigail Blake‐Bradshaw; Dmitrijs Boiko; Nelleke H. Buitendijk; Jeffrey J. Buler; et al. (Ecology Letters, 2026)
Animal movements contribute to the spread of infectious diseases and are driven in part by environmental conditions. We investigated the links among the environment, animal movement, and infectious disease dynamics in waterfowl, which are among the primary wildlife hosts of avian influenza viruses. By combining telemetry data on 4606 individuals from 26 waterfowl species with data on land cover, weather, and vegetation, we found that waterfowl moved less in areas of higher land cover heterogeneity and higher human population density. Moreover, predicted waterfowl movement distances were weakly but positively correlated with distances between detections of H5N1 highly pathogenic avian influenza in wild waterfowl, suggesting that environmental conditions might contribute to the spread of this disease via their effects on bird movements. By considering wildlife movements alongside other drivers of infectious disease dynamics, such as livestock production and human mobility, we move closer to predicting outbreaks and informing interventions.

Myrcene suppressed fever by downregulating systemic TNF-α levels in acute LPS-induced systemic inflammation in rats - Maycon T. Emilio-Silva; Vinicius P. Rodrigues; Mariana M. Fioravanti; Luiz G. S. Branco; Clelia A. Hiruma-Lima (Advances in Traditional Medicine, 2025)

Development of fluids containing silicon dioxide extracted from Agro-Industry waste and tamarind gum for wettability alteration of carbonate rocks - Maria Eduarda R. Vaz; Priscila F. Oliveira; Carolina R.A. Cruz; Letícia Cristina A. Sanches; Raissa T. Rodrigues; Luiz Carlos M. Palermo; Claudia R.E. Mansur (Fuel, 2025)

Individual and combined effects of a simulated heatwave and the emerging Phytophthora ×multiformis on European alder species - I. Gomes Marques; C. Vieites-Blanco; M.J. Barrento; A. Cupertino; J.N. Semedo; A.P. Rodrigues; P. Scotti-Campos; T. Jung; A. Solla; T.S. David; P.M. Rodríguez-González (Forest Ecology and Management, 2025)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Harnessing organoid technology to model autoimmune pathways in rheumatological and inflammatory disorders - Amr Ali Mohamed Abdelgawwad El-Sehrawy; Teeba Ammar Rashid; Paul Rodrigues; Baneen C. Gabaal; Suhas Ballal; Abhayveer Singh; T. KRITHIGA; Mehul Manu; N. Esanmurodova; Jamal K. Abbas (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Komagataella pastoris KM71H Attenuates Cognitive Deficits and Depressive-Like Behavior by the TLR4/NF-κB Signaling Pathway in an Aβ1-40-Induced AD-Like Mouse Model - Paloma T. Birmann; Giuliana Petiz Zugno; Airton Sinott; Rafael R. Rodrigues; Fabricio R. Conceição; Fernanda Severo Sabedra Sousa; Tiago Collares; Fabiana K. Seixas; Lucielli Savegnago (Molecular Neurobiology, 2025)

Uncovering neotropical rock geckos’ diversity: multiple data sources on an integrated taxonomic approach reveal a new species of Phyllopezus Peters, 1878 (Squamata: Phyllodactylidae) from northeastern Brazilian Atlantic Forest - Marcos J.M. Dubeux; Gisele M.N. Vieira Dubeux; Jessika M.M. Neves; Fernanda P. Werneck; Miguel T. Rodrigues; Tamí Mott; Pedro M.S. Nunes (Zoologischer Anzeiger, 2025)

Ultrasound-enhanced bioaccessibility and pharmacological activities of curcumin in inclusion complexes - Matheus X. Oliveira; Irisvan S. Ribeiro; Francisca Vanessa C. Canafístula; Stephanie Ferreira M. Muniz; Lorena Maria F. Sampaio; Alyne Rodrigues A. Nobre; Fábio Oliveira S. Ribeiro; Raí E. Silva; Jessica Maria T. Souza; Erick Joniher B. Torres; José Delano Barreto M. Filho; Ana J. Araújo; et al. (Food Chemistry, 2025)

Risks of exceeding health-based guidance values for toxic metals and metalloids through seaweed and halophyte consumption - Elsa T. Rodrigues; Leonel Pereira; Eduarda Pereira; Miguel A. Pardal (Food Control, 2025)

Metabolomic profiles and antioxidant intake in female soccer players: a cross-sectional study - M. M. S. Gouveia; M. B. A. Nascimento; A. C. Crispim; E. R. da Rocha; M. P. P. Santos; E. S. Bento; T. M. Aquino; P. Balikian; N. A. Rodrigues; T. Ataide-Silva; G. G. de Araujo; F. A. B. Sousa (European Journal of Applied Physiology, 2025)

Tides of rebirth: A stratigraphic perspective on the Lazarus effect in freshwater bivalves in the Aptian-Albian Romualdo Formation, Araripe Basin, Brazil - Marcello G. Simões; Vitor B. Guerrini; Victor R. Silva; Filipe G. Varejão; Suzana A. Matos; Mariza G. Rodrigues; Lucas V. Warren; Mario L. Assine; Franz T. Fürsich (Cretaceous Research, 2025)

Ancient Introgression Explains Mitochondrial Genome Capture and Mitonuclear Discordance Among South American Collared Tropidurus Lizards - Matheus M. A. Salles; André L. G. Carvalho; Adam D. Leaché; Nicolas Martinez; Frederick Bauer; Martha Motte; Viviana Espínola; Miguel T. Rodrigues; Carla Piantoni; Marcio R. Pie; André Olivotto; Guarino R. Colli; et al. (Molecular Ecology, 2025)
Mitonuclear discordance—evolutionary discrepancies between mitochondrial and nuclear DNA phylogenies—can arise from various factors, including introgression, incomplete lineage sorting, recent or ancient demographic fluctuations, sex‐biased dispersal asymmetries, among others. Understanding this phenomenon is crucial for accurately reconstructing evolutionary histories, as failing to account for discordance can lead to misinterpretations of species boundaries, phylogenetic relationships, and historical biogeographic patterns. We investigate the evolutionary drivers of mitonuclear discordance in the Tropidurus spinulosus species group, which contains nine species of lizards inhabiting open tropical and subtropical environments in South America. Using a combination of population genetic and phylogenomic approaches applied to mitochondrial and nuclear data, we identified different instances of gene flow that occurred in ancestral lineages of extant species. Our results point to a complex evolutionary history marked by prolonged isolation between species, demographic fluctuations, and potential episodes of secondary contact with genetic admixture. These conditions likely facilitated mitochondrial genome capture while diluting signals of nuclear introgression. Furthermore, we found no strong evidence supporting incomplete lineage sorting or natural selection as primary drivers of the observed mitonuclear discordance. Therefore, the unveiled patterns are most consistent with neutral demographic processes, coupled with ancient mitochondrial introgression, as the main factors underlying the mismatch between nuclear and mitochondrial phylogenies in this system. Future research could further explore the role of other demographic processes, such as asymmetric sex‐biased dispersal, in shaping these complex evolutionary patterns.

Shared mobility during public transport disruptions: Users’ perspectives in a Brazilian city - Luiza Gagno Azolin; Anna Beatriz Grigolon; Antônio Nélson Rodrigues da Silva; Karst T. Geurs (Transportation Research Part D: Transport and Environment, 2025)

Recovery of tree species functional composition in eucalypt plantations with natural regeneration differs among canopy strata - Laura H.P. Simões; Marielos Peña-Claros; Joannès Guillemot; Rens Brouwer; Frans Bongers; Lourens Poorter; Catherine T. de Almeida; Danilo R.A. Almeida; Miguel Cooper; Mathieu Decuyper; José G. Fernandes Neto; Matheus S. Fuza; et al. (Forest Ecology and Management, 2025)

Amazonian trees functional adjustments to long term experimental drought are limited and species dependent - Vanessa Negrão-Rodrigues; Paulo Bittencourt; Pablo Sanchez-Martinez; Lucy Rowland; Lion R. Martius; Patrick Meir; Manolo T. Quintilhan; José Roberto V. Aragão; Victor Brigatto; Vinicius D. Oliveira; Peter Groenendijk; Arlete A. Soares; et al. (Flora, 2025)

Exploring In Vitro Mesenchymal Stem Cell Osteodifferentiation via Vibrational Microspectroscopy: A Review - Daniela S. Bispo; Inês C. R. Graça; João A. Rodrigues; João T. S. Martins; Mariela M. Nolasco; Maria P. M. Marques; Helena I. S. Nogueira; João F. Mano; Mariana B. Oliveira; Paulo J. A. Ribeiro-Claro; Ana M. Gil (Stem Cell Reviews and Reports, 2025)
The application of vibrational microspectroscopy to the study of in vitro mesenchymal stem cells (MSC) osteogenic differentiation is a promising approach towards the understanding of the molecular processes involved in bone fabrication. Both infrared (IR) and Raman microspectroscopies have been applied, with a clear predominance of the latter. Bone marrow MSC have been the target of most studies, followed by those originating from dental/oral and adipose tissues. Interests have increasingly addressed single cell and extracellular matrix characterization at the molecular level. Most studies have focused on the characteristics and maturity of time-course mineralization, attempting to localize mineral aggregates formed onto the evolving collagen strands. Some reports have focused on time-dependent changes in protein structure and other components of extracellular matrix components. Besides spectral band examination through position, linewidth and shape, selected band ratios have proved largely informative to assess mineral species evolution and mineral-to-organic matrix interactions over time. The increasing use of multivariate analysis (or chemometrics) and machine learning strategies to detect finer spectral variations is evident, as is the promise of more recent IR and Raman variations to provide higher sensitivity and spatial resolution conditions. The label-free non-invasive nature of vibrational microspectroscopy makes it particularly promising for rapid and effective selection of suitable MSC donors, to support scale-up procedures for translation to the clinic. Some of the challenges to be faced are briefly discussed. Graphical Abstract

Combination therapies and novel delivery systems: a new frontier in overcoming TRAIL resistance in gastric cancer - Paul Rodrigues; Abdulrahman T. Ahmed; Majid Jabir; Khetam Habeeb Rasool; Soumya V. Menon; Aryantika Sharma; M. Ravi Kumar; Matheel D. Al-Sabti; Sabrean F. Jawad; Salah Hassan Zain Al-Abdeen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Recovery of below-ground associations in restored Brazilian Atlantic Forest - Luis Fernando Merloti; Raúl Ochoa-Hueso; Dina in 't Zandt; G.F. (Ciska) Veen; Wanderlei Bieluczyk; Ricardo Ribeiro Rodrigues; Lucas William Mendes; Siu Mui Tsai; Wim H. van der Putten (Applied Soil Ecology, 2025)

Temporal dynamics of class 1 and class 3 integron pools in treated wastewater - Rafael D.S. Tavares; Elsa T. Rodrigues; Marta Tacão; Isabel Henriques (Water Research, 2025)

P04-05 Time-resolved reprogramming of metabolism in rats exposed to air pollutants: a serum NMR metabolomics approach for the investigation of dose-response and hazard assessment - B. Métoyer; N. Chouan; B. Rival; M. Cherrière; A. Lecomte; F. Robidel; S. Rodrigues; M. Floreani; G. Barbier; G. Lacroix; T. Loret; M. Valente; et al. (Toxicology Letters, 2025)

Assessing blue carbon sink through the soil decomposition processes in tropical monsoon (Amazon) and Semiarid mangroves - N. Beloto; M.R. Gmach; L.C. Cotovicz Jr.; T. Giarrizzo; G.N. Nóbrega; T. Pegado; J.V.M. Rodrigues; M.O. Soares; F.C.S. Nascimento; R.D. Ward; L.E.A. Bezerra (Regional Studies in Marine Science, 2025)

Multistage treatment system integrating constructed wetlands and microalgae for wastewater reuse and bioenergy recovery - Gustavo S. Colares; Luana T. Junqueira; Fernanda N. Brum; Romualdo J.C. Wanderley; Tainá Conzatti; Lenin D. Garcia; Lucia H.R. Rodrigues; Carlos A. Lutterbeck; Ênio L. Machado; Odorico Konrad (Journal of Water Process Engineering, 2025)

Fermented brewer's spent grain as a sustainable feed ingredient impacts meagre (Argyrosomus regius) growth, intermediary metabolism, digestive enzymes, oxidative stress, and intestinal histology - T. Estevão-Rodrigues; H. Fernandes; S. Moutinho; A. Couto; I. Belo; C. Castro.; P. Pousão; J.M. Salgado; A. Oliva-Teles; H. Peres (Animal Feed Science and Technology, 2025)

Comparisons of Hyperostotic Bones in Two Species of the Genus Oligoplites Gill, 1863 in the Southern Brazilian Coast - Fernando A. P. Tuna; Ana Paula C. de Rodrigues; Gustavo P Filgueira; Rebeca s da Bianca; Wilson T. V. Machado; Márcia C. Salomão; Helena P. Lavrado (Journal of Fish Diseases, 2025)
The description of skeletal disorders is commonly reported in fish species raised through aquaculture; however, wild marine fish may also exhibit high frequencies of anomalies, particularly the development of hyperostosis, a condition that causes thickening of the bones. Specimens of Oligoplites saliens ( n = 15) and Oligoplites palometa ( n = 14) were radiographed to verify hyperostotic bone occurrences. Hyperostosis was detected in all individuals (> 400 mm TL) analysed for both species, occurring in six distinct regions of the skeleton (supraoccipital bone, cleithrum, dorsal pterygiophores, anal pterygiophore, haemal spines, and neural spines), regardless of the sex of the individuals. No hyperostosis was found in the neural and haemal spines of O. palometa and in the anal pterygiophore of O. saliens . Histological sections of the supraoccipital bone of O. saliens were conducted, revealing high porosity characterised by the presence of vascular channels in bones with hyperostosis. The species exhibited species‐specific patterns for the condition, demonstrating differences even among species of the same genus occurring in the same geographic area. This is the first record of hyperostosis for both species in Brazilian waters.

LDL Exposure Disrupts Mitochondrial Function and Dynamics in a Hippocampal Neuronal Cell Line - Hémelin Resende Farias; Jessica Marques Obelar Ramos; Caroline Tainá Griesang; Lucas Santos; Osmar Vieira Ramires Junior; Debora Guerini Souza; Fernanda Silva Ferreira; Sabrina Somacal; Leo Anderson Meira Martins; Diogo Onofre Gomes de Souza; José Cláudio Fonseca Moreira; Angela T. S. Wyse; et al. (Molecular Neurobiology, 2025)

Cultivation of Gelidium floridanum in different nitrate concentrations: morphophysiological effects - Mariana F. Carvalho; Gabriela Rodrigues; Debora T. Pereira; Deonir Batista; Luciane C. Ouriques; Carmen Simioni (Journal of Applied Phycology, 2025)

The caatinga dry tropical forest: A highly efficient carbon sink in South America - Keila R. Mendes; Pablo E.S. Oliveira; José Romualdo S. Lima; Magna S.B. Moura; Eduardo S. Souza; Aldrin M. Perez-Marin; John Elton B.L. Cunha; Pedro R. Mutti; Gabriel B. Costa; Thales N. Martins de Sá; Paula A.A. Araujo; Rosaria R. Ferreira; et al. (Agricultural and Forest Meteorology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Do behavioral attitudes of livestock farmers in Cameroon influence the adoption of insect-based feed? An application of the theory of planned behavior - Ruth T. Nembu; Boris D. Soh Wenda; Hervé K. Mube; Hervé W. Napi; Shaphan Y. Chia; Sali A. Ndindeng; Rodrigue B. Kamga; Dorothy E. Fon (Food and Humanity, 2025)

Estimation of diurnal and nocturnal radiation balance in tropical ecosystems - D. O. Maionchi; I. J. C. de Paulo; S. R. de Paulo; J. B. Marques; A. L. P. Junior; H. J. A. da Silva; R. S. Palácios; T. R. Rodrigues; T. A. dos Santos; A. M. S. Lima; M. S. Biudes; L. Sanches; et al. (Theoretical and Applied Climatology, 2025)

Self-assembly and 3D Bioprinting of Neurospheres and Evaluation of Caffeine and Photobiomodulation Effects in an Alzheimer’s Disease In Vitro Model - Geisa Rodrigues Salles; Alessandro E. C. Granato; Fernanda Tibolla Viero; Cristina Pacheco-Soares; Sérgio T. Ferreira; Marimelia Porcionatto; Henning Ulrich (Stem Cell Reviews and Reports, 2025)

Porcine circovirus type 2 (PCV2) in Brazil in the past 55 years (1967-2022): evolutionary rates and patterns - I. L. F. Rodrigues; A. C. M. Cruz; A. E. Souza; F. B. Knackfuss; C. H. C. Costa; B. V. Lago; R. L. Silveira; T. X. Castro (Archives of Virology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Correction to: Potential of Marine Strains of Pseudoalteromonas to Improve Resistance of Juvenile Sea Bass to Pathogens and Limit Biofilm Development - A. Rahmani; L. Parizadeh; M. Baud; Y. Francois; A. Bazire; S. Rodrigues; Y. Fleury; H. Cuny; E. Debosse; J. Cabon; L. Louboutin; L. Bellec; et al. (Probiotics and Antimicrobial Proteins, 2025)

Potential of Marine Strains of Pseudoalteromonas to Improve Resistance of Juvenile Sea Bass to Pathogens and Limit Biofilm Development - A. Rahmani; L. Parizadeh; M. Baud; Y. Francois; A. Bazire; S. Rodrigues; Y. Fleury; H. Cuny; E. Debosse; J. Cabon; L. Louboutin; L. Bellec; et al. (Probiotics and Antimicrobial Proteins, 2025)

Neuroinflammation in Severe COVID-19: The Dynamics of Inflammatory and Brain Injury Markers During Hospitalization - Carla Andretta Moreira Neves; Gilson P. Dorneles; Paula C. Teixeira; Paulo C. Santana Filho; Alessandra Peres; Carina Rodrigues Boeck; Liane N. Rotta; Claudia E. Thompson; Pedro R. T. Romão (Molecular Neurobiology, 2025)

Accessibility of polycyclic aromatic hydrocarbon content in fishes from the region of the 2019 oil spill on the northeast Brazil coast - Abinoan S. Rodrigues; Thayane Cristina da S. Moreira; Rafael Garrett Dolatto; Jandyson Machado Santos; Marco T. Grassi; Licarion Pinto; Ana Paula S. Paim (Marine Pollution Bulletin, 2025)

Tailoring a lignocellulosic biomass to simultaneously enhance N-doping and textural properties of porous carbons designed for effective environmental remediation - Letícia D. Capel; Liriana M. Roveda; Claudio T. Carvalho; Magno A.G. Trindade; Robson M. da Silva; Raphael Rodrigues (Environmental Research, 2025)

Disclosing surface functionality evolution in H2SO4-assisted hydrothermally carbonized lignocellulosic precursors: Deciphering the roles of lignin and cellulose - José L.B. Campos; Paulo H.L. Pinheiro; Robson M. da Silva; Claudio T. Carvalho; Magno A.G. Trindade; Raphael Rodrigues (Fuel, 2025)

Ceftazidime-avibactam tolerance and persistence among difficult-to-treat KPC-producing Klebsiella pneumoniae clinical isolates from bloodstream infections - N. Abichabki; G. G. Gaspar; L. R. Bortolato; D. A. F. S. Lima; L. N. Silva; R. H. C. Pocente; J. C. Ferreira; T. C. Ogasawara; D. Pereira; R. R. Guerra; C. Wilhelm; P. Barth; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Periovulatory anticoagulant therapy enhances embryo recovery rates in superovulated mares - Lucas T. Rodrigues; Lorenzo Segabinazzi; Mariana Frasson; Camila Dell’Aqua; Marcio T. Carmo; Regina K. Takahira; Marco Alvarenga; Frederico Papa (Theriogenology, 2025)

Elevational Range Impacts Connectivity and Predicted Deme Sizes From Models of Habitat Suitability - Connor M. French; Roberta P. Damasceno; Mariana M. Vasconcellos; Miguel T. Rodrigues; Ana C. Carnaval; Michael J. Hickerson (Molecular Ecology, 2025)
In integrative distributional, demographic and coalescent (iDDC) modelling, a critical component is the statistical relationship between habitat suitability and local population sizes. This study explores this relationship in two Enyalius lizard species from the Brazilian Atlantic Forest: the high‐elevation E. iheringii and low‐elevation E. catenatus and how this transformation affects spatiotemporal demographic inference. Most previous iDDC studies assumed a linear relationship, but this study hypothesises that the relationship may be nonlinear, especially for high‐elevation species with broader environmental tolerances. We test two key hypotheses: (1) The habitat suitability to population size relationship is nonlinear for E. iheringii (high‐elevation) and linear for E. catenatus (low‐elevation); and (2) E. iheringii exhibits higher effective migration across populations than E. catenatus . Our findings provide clear support for hypothesis (2), but mixed support for hypothesis (1), with strong model support for a nonlinear transformation in the high‐elevation E. iheringii and some (albeit weak) support for a nonlinear transformation also in E. catenatus . The iDDC models allow us to generate landscape‐wide maps of predicted genetic diversity for both species, revealing that genetic diversity predictions for the high‐elevation E. iheringii align with estimated patterns of historical range stability, whereas predictions for low‐elevation E. catenatus are distinct from range‐wide stability predictions. This research highlights the importance of accurately modelling the habitat suitability to population size relationship in iDDC studies, contributing to our understanding of species' demographic responses to environmental changes.

Integrative species delimitation and biogeography of the Rhinella margaritifera species group (Amphibia, Anura, Bufonidae) suggest an intense diversification throughout Amazonia during the last 10 million years - Antoine Fouquet; Miqueias Ferrão; Miguel T. Rodrigues; Fernanda P. Werneck; Ivan Prates; Leandro J.C.L. Moraes; Tomas Hrbek; Juan C. Chaparro; Albertina P. Lima; Renata Perez; Andre Pansonato; Vinicius T. Carvalho; et al. (Systematics and Biodiversity, 2024)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Comparing net zero pathways across the Atlantic A model inter-comparison exercise between the Energy Modeling Forum 37 and the European Climate and Energy Modeling Forum - Luis Sarmiento; Johannes Emmerling; Robert Pietzcker; Vassilis Daioglou; Francesco Dalla Longa; Mark M. Dekker; Laurent Drouet; Amir Fattahi; Panagiotis Fragkos; Hauke T. J. Henke; Oliver Fricko; Leonard Göke; et al. (Energy and Climate Change, 2024)

RecQ helicase expression in patients with telomeropathies - João Paulo L. Silva; Flávia S. Donaires; Fernanda Gutierrez-Rodrigues; Davi J. Martins; Vinicius S. Carvalho; Barbara A. Santana; Renato L. G. Cunha; Sachiko Kajigaya; Carlos F. M. Menck; Neal S. Young; Eigil Kjeldsen; Rodrigo T. Calado (Molecular Biology Reports, 2024)

Plastisphere in a low-pollution mountain river: Influence of microplastics on survival of pathogenic bacteria - Isabel Silva; Elsa T. Rodrigues; Marta Tacão; Isabel Henriques (Chemosphere, 2024)

Characterization and kinetics of whey protein isolate amyloid fibril aggregates under moderate electric fields - Rita T. Leal; Ricardo S. Pereira; Rui M. Rodrigues; Ricardo N. Pereira (Food Research International, 2024)

Occurrence and potential ecological risks of PFAS in Pampulha Lake, Brazil, a UNESCO world heritage site - Maria Clara V.M. Starling; Daniel A.S. Rodrigues; Gisele A. Miranda; Suna Jo; Camila C. Amorim; Gerald T. Ankley; Matt Simcik (Science of The Total Environment, 2024)

Holistic evaluation of the environmental impacts of shipping in the sensitive region of Ria de Aveiro - A. Monteiro; V. Rodrigues; A. Picado; J.M. Dias; N. Abrantes; A. Ré; M. Rosa; M. Russo; A. Barreirinha; M. Potiris; M. Aghito; R. Hänninen; et al. (Science of The Total Environment, 2024)

The ADnet Bayesian belief network for alder decline: Integrating empirical data and expert knowledge - Inês Gomes Marques; Cristina Vieites-Blanco; Patricia M. Rodríguez-González; Pedro Segurado; Marlene Marques; Maria J. Barrento; Maria R. Fernandes; Arthur Cupertino; Helena Almeida; Idoia Biurrun; Tamara Corcobado; Filipe Costa e Silva; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Portuguese macroalgae and halophytes for human consumption: Minimal risk of norovirus and Salmonella infection - Joana M. Oliveira; Miguel A. Pardal; Leonel Pereira; Ana M. Matos; Elsa T. Rodrigues (Food Control, 2024)

Gut colonization by extended-spectrum β-lactamase-producing Escherichia coli in dairy herd in Brazil: successful dissemination of a One Health clone - Luciana Sartori; Fábio P. Sellera; Taiana T. Silva-Pereira; Bruna Fuga; Danny Fuentes-Castillo; Milena Dropa; Quézia Moura; Miriam R. Fernandes; Larissa Rodrigues; Fernanda Esposito; Elder Sano; Mario A. R. Aleman; et al. (Veterinary Research Communications, 2024)

Analysis of environmental variables and deforestation in the amazon using logistical regression models - Helder J. F. da Silva; Weber A. Gonçalves; Bergson G. Bezerra; Cláudio M. Santos e Silva; Cristiano P. de Oliveira; Jório B. Cabral Júnior; Daniele T. Rodrigues; Fabrício D. S. Silva (Environmental Monitoring and Assessment, 2024)

S05-03 The development of a human liver-based In Vitro test battery to detect liver steatotic potential of chemicals from various applicability domains - A. Verhoeven; A. Drees; A. Gatzios; R.M. Rodrigues; J. Sanz-Serrano; A. Tabernilla; T. Vanhaecke; M. Vinken (Toxicology Letters, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Bioactivity of Piper aduncum and Piper marginatum essential oils on Planococcus citri (RISSO, 1813) (Hemiptera: Pseudococcidae) - Carla H. M. De Lima; Claudio A. G. Camara; Vaneska B. Monteiro; Mayara F. Santos; Wendel J. T. Pontes; Marcílio M. Moraes; Lucas V. B. Rodrigues (International Journal of Tropical Insect Science, 2024)

The thermal equation of state of xenon: Implications for noble gas incorporation in serpentine minerals and their transport to depth - A.D. Rosa; F. Zecchi; P. Condamine; M.A. Bouhifd; J.E.F.S. Rodrigues; E. Mijit; T. Irifune; O. Mathon; G. Garbarino; M. Mezouar; A. Dewaele; N. Ishimatsu (Geochimica et Cosmochimica Acta, 2024)

Integron-associated genes are reliable indicators of antibiotic resistance in wastewater despite treatment- and seasonality-driven fluctuations - Rafael D.S. Tavares; Cátia Fidalgo; Elsa T. Rodrigues; Marta Tacão; Isabel Henriques (Water Research, 2024)

Nitrogen efficiency indices for sustainable sweet potato production in tropical environments - Adalton M. Fernandes; Patricio Sandaña; Rogério P. Soratto; Nathalia P. Ribeiro; Fabricio E. Rodrigues; Ítala T. Guimarães (Field Crops Research, 2024)

Collapse mechanisms and fragility curves based on Lumped Damage Mechanics for RC frames subjected to earthquakes - Rúbia M. Bosse; Julio Flórez-López; Gustavo M.S. Gidrão; Isabela Durci Rodrigues; André T. Beck (Engineering Structures, 2024)

Saline as solvent and ethanol-based purification process for the extraction of proteins and isoflavones from wet okara - Rafaela T. Privatti; Maria C. Capellini; Keila K. Aracava; Silvana M.P. Pugine; Mariza P. de Melo; Christianne E.C. Rodrigues (Food Chemistry, 2024)

Erythropoietin effects on cryopreserved/transplanted cat ovarian tissue: A comparison of two incubation methods - Isabella M.G. Silva; Aline Q. Rodrigues; Rayane B. Ribeiro; Beatriz A. Aguiar; Anne E.S.P. Marinho; Elisa A.M. Souza; Yasmin B. Ferreira; Victoria C.O. Azevedo; Daniela M. Oliveira; Sônia N. Báo; Jair T. Goulart; Carolina M. Lucci; et al. (Cryobiology, 2024)

Kinematics of the Clarke River Shear Zone (northeastern Australia) and implications for the tectonic evolution of the Tasmanides - R. T. Rodrigues; G. Rosenbaum; R. Abdullah (Australian Journal of Earth Sciences, 2024)

Omega-3 fatty acids from fish by-products: Innovative extraction and application in food and feed - Matilde Rodrigues; Ana Rosa; André Almeida; Rui Martins; T.ânia Ribeiro; Manuela Pintado; Raquel F.S. Gonçalves; Ana C. Pinheiro; António J.M. Fonseca; Margarida R.G. Maia; Ana R.J. Cabrita; Lillian Barros; et al. (Food and Bioproducts Processing, 2024)

The vicariant role of Caribbean formation in driving speciation in American loliginid squids: the case of Doryteuthis pealeii (Lesueur 1821) - João Bráullio Luna Sales; Frank E. Anderson; Bianca Lima Paiva; Yasmim T. C. Cunha; Alan Érik Souza Rodrigues; Yrlene Ferreira; Luis Fernando S. Rodrigues-Filho; Paul W. Shaw; Manuel Haimovici; Unai Markaida; Jonathan S. Ready; Iracilda Sampaio (Marine Biology, 2024)

Microrheological characterisation of Cyanoflan in human blood plasma - T. Rodrigues; R. Mota; L. Gales; P. Tamagnini; L. Campo-Deaño (Carbohydrate Polymers, 2024)

Dynamics of CO2, CH4, and N2O in Ria Formosa coastal lagoon (southwestern Iberia) and export to the Gulf of Cadiz - A. Sierra; C. Correia; T. Ortega; J. Forja; M. Rodrigues; A. Cravo (Science of The Total Environment, 2024)

Effects of feeding mycotoxin-contaminated diets and the use of an adsorbent on the intake, digestibility, rumen fermentation, nitrogen balance and physiological parameters in the blood of Nellore steers - Luis Henrique C. Batista; Gustavo R. Siqueira; Luiz F. Costa e Silva; Anne Koontz; Yury T. Granja-Salcedo; Igor M. Ferreira; Iorrano A. Cidrini; Karla A. Oliveira; Amanda Caroliny M. de Queiroz; Aline N. Rodrigues; Flávio D. de Resende (Animal Feed Science and Technology, 2024)

Effects of chemical aging on carbonaceous materials: Stability of water-dispersible colloids and their influence on the aggregation of natural-soil colloid - Laís G. Fregolente; Maria T. Rodrigues; Naiara C. Oliveira; Bruno Sousa Araújo; Ícaro V. Nascimento; Antonio G. Souza Filho; Amauri J. Paula; Mirian C.G. Costa; Jaedson C.A. Mota; Odair P. Ferreira (Science of The Total Environment, 2023)

Identifying imprints of externally derived dust and halogens in the sedimentary record of an Iberian alpine lake for the past ∼13,500 years – Lake Peixão, Serra da Estrela (Central Portugal) - J. Moreno; A.M. Ramos; P.M. Raposeiro; R.N. Santos; T. Rodrigues; F. Naughton; F. Moreno; R.M. Trigo; J. Ibañez-Insa; P. Ludwig; X. Shi; A. Hernández (Science of The Total Environment, 2023)

Glycerol-based H3PO4-activated carbon as a versatile adsorbent for removal of pollutants from wastewater: A novel synthesis protocol - Iveth A. da Silva; Liriana M. Roveda; Claudio T. Carvalho; Magno A.G. Trindade; Robson M. da Silva; Raphael Rodrigues (Environmental Nanotechnology, Monitoring & Management, 2023)

Protocols for the seminal cryopreservation of South American catfishes – current status - Danilo P. Streit; Rômulo B. Rodrigues; Eduardo A. Sanches; Jayme A. Povh; Diógenes H. Siqueira-Silva; Thaíza R. de Freitas; Nathalia T. Santos; Jhony B. Lisboa; Thales S. França; Eduardo Nicoleti; Larise O.C. Lima; Tiantian Zhang (Cryobiology, 2023)

The H9c2(2-1) cell-based sulforhodamine B assay is a non-animal alternative to evaluate municipal wastewater quality over time - Elsa T. Rodrigues; Eduarda Pereira; Paulo J. Oliveira; Miguel A. Pardal (Environmental Monitoring and Assessment, 2023)
The present study validates the potential of the in vitro H9c2(2-1) cell-based sulforhodamine B (SRB) assay to evaluate the temporal variability of wastewater quality. The impact of effluent disposal on water quality and the efficiency of the wastewater treatment process were also assessed. To correlate standard analytical method results with in vitro results, a total of 16 physicochemical parameters, such as nutrients, pH, chemical oxygen demand, total suspended solids and metals, were determined in both raw and treated wastewater samples. Results revealed that the H9c2(2-1) cell-based SRB assay has an enormous potential to evaluate municipal wastewater quality over time and to discriminate influent and effluent toxic characteristics, as well as for water quality monitoring and surveillance of the efficacy of treatment processes. Finally, the gathered results alerted to the impact of phosphates in a biological system, leading us to recommend the selection of this parameter as a potential environmental health indicator.

Bioaccumulation and speciation of arsenic in plankton from tropical soda lakes along a salinity gradient - José Lucas Martins Viana; Débora Aparecida Steffler; Amauris Hechavarría Hernández; Juliana dos Santos Costa; Thierry Alexandre Pellegrinetti; Erick Christian Rodrigues de Jesus; Marianna Cancian; Marli Fátima Fiore; Ary T. Rezende-Filho; Alessandra Sussulini; Laurent Barbiero; Amauri Antonio Menegario; et al. (Science of The Total Environment, 2023)

Flexible thermoelectric energy harvesting system based on polymer composites - T. Rodrigues-Marinho; V. Correia; C.-R. Tubio; A. Ares-Pernas; M.-J. Abad; S. Lanceros-Méndez; P. Costa (Chemical Engineering Journal, 2023)

P06-04: Development of the TOXIN Knowledge Graph for assisting animal-free risk assessment of cosmetic ingredients - S. Sepehri; J. Maushagen; G. Vrijens; C. Debruyne; R. Marcelino Rodrigues; A. Sanctorum; O. De Troyer; T. Vanhaecke (Toxicology Letters, 2023)

P01-02: An updated adverse outcome pathway network on chemical-induced liver steatosis - A. Verhoeven; J. van Ertvelde; J. Boeckmans; A. Gatzios; R. Jover; B. Lindeman; G. Lopez Soop; R. Marcelino Rodrigues; A. Rapisarda; M. Stinckens; S. Sepehri; M. Vinken; et al. (Toxicology Letters, 2023)

Trace elements, C–O isotopes and U–Pb geochronology of the Minas Supergroup in the Segredo deposit, Quadrilátero Ferrífero, Brazil - Janaina Rodrigues De Paula; Fabricio A. Caxito; Alcides N. Sial; Diniz T. Ribeiro; Ana Ramalho Alkmim; Cristiano Lana; Issamu Endo (Journal of South American Earth Sciences, 2023)

Microplastics accumulate priority antibiotic-resistant pathogens: Evidence from the riverine plastisphere - Isabel Silva; Elsa T. Rodrigues; Marta Tacão; Isabel Henriques (Environmental Pollution, 2023)

Separation of alkane isomers in a hierarchically structured 3D-printed porous carbon monolith - Adriano Henrique; Hendryk Steldinger; Jose L. Diaz de Tuesta; Jan Gläsel; Alírio E. Rodrigues; Helder T. Gomes; Bastian J.M. Etzold; José A.C. Silva (Chemical Engineering Journal, 2023)

Behavior of deteriogenic fungi in aviation fuels (fossil and biofuel) during simulated storage - Mariane Rodrigues Lobato; Juciana Clarice Cazarolli; Regiane Débora Fernandes Rios; Emmanuel Bezerra D’ Alessandro; Marcia T. S Lutterbach; Nelson Roberto Antoniosi Filho; Vânya Márcia Duarte Pasa; Donato Aranda; Pedro Rodrigo Scorza; Fátima Menezes Bento (Brazilian Journal of Microbiology, 2023)

Different patterns of maize hybrids responses under variable phosphorus availability - R. E. Rodrigues; A. R. Neto; L. S. Jesus; L. T. M. Guedes; L. S. Santos; M. N. Xavier; L. A. Souza (Acta Physiologiae Plantarum, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Detailed characterization of iron-rich tailings after the Fundão dam failure, Brazil, with inclusion of proximal sensors data, as a secure basis for environmental and agricultural restoration - Rafaella T. Silva de Sá; Marcelo Tesser Antunes Prianti; Renata Andrade; Aline Oliveira Silva; Éder Rodrigues Batista; Jessé Valentim dos Santos; Fernanda Magno Silva; Marco Aurélio Carbone Carneiro; Luiz Roberto Guimarães Guilherme; Somsubhra Chakraborty; David C. Weindorf; Nilton Curi; et al. (Environmental Research, 2023)

An exonuclease V homologue is expressed predominantly during early megasporogenesis in apomictic Brachiaria brizantha - Diva M. A. Dusi; Elizângela R. Alves; Gláucia B. Cabral; Luciane V. Mello; Daniel J. Rigden; Érica D. Silveira; Márcio Alves-Ferreira; Larissa A. Guimarães; Ana Cristina M. M. Gomes; Júlio C. M. Rodrigues; Vera T. C. Carneiro (Planta, 2023)

Komagataella pastoris KM71H Mitigates Depressive-Like Phenotype, Preserving Intestinal Barrier Integrity and Modulating the Gut Microbiota in Mice - Paloma T. Birmann; Angela M. Casaril; Ana Paula Pesarico; Rafael R. Rodrigues; Fabricio R. Conceição; Fernanda Severo Sabedra Sousa; Tiago Collares; Fabiana K. Seixas; Lucielli Savegnago (Molecular Neurobiology, 2023)

A new species of mailed catfish of genus Rhadinoloricaria (Siluriformes: Loricariidae: Loricariinae) from Rio Negro basin, Brazil - Jefferson L. Crispim‐Rodrigues; Maxwell J. Bernt; Brandon T. Waltz; Gabriel S. C. Silva; Ricardo C. Benine; Claudio Oliveira; Raphaël Covain; Fábio F. Roxo (Journal of Fish Biology, 2023)
During a recent collection expedition to the Rio Negro, in the state of Amazonas, Brazil, eight individuals of an unknown species were collected, with a combination of characteristics that placed the species in the genus Rhadinoloricaria . Furthermore, the presence of two autapomorphic characteristics, including numerous elongated papillae on the lower lip and unbranched barbelets on the margin of lower lip, suggests that it is a new species. From morphological and phylogenetic analyses, including the sequencing of specific genes to calculate the maximum likelihood analyses, coupled with osteological computed tomography (CT) scan analyses, the authors corroborated that the specimens represent a new species of Rhadinoloricaria , described in the present study.

A sequential recovery extraction and biological activity of water-soluble sulfated polysaccharides from the polar red macroalgae Sarcopeltis skottsbergii - Pablo Castro-Varela; Mónica Rubilar; Bruna Rodrigues; María Jesús Pacheco; Candela T. Caneda-Santiago; Manuel Marí-Beffa; Félix L. Figueroa; Roberto Abdala-Díaz (Algal Research, 2023)

Monitoring the impacts of a mega-dam on Amazonian understorey herbs - Marcelo B. Medeiros; Washington L. Oliveira; Flávio R.O. Rodrigues; Renata D. Silva; Íris J.K. Ferreira; Wellyngton E. Ayala; Suelma R. Silva; Rafaela T. Souza; Marcelo F. Simon (Forest Ecology and Management, 2023)

Controlled lipid self-assembly for scalable manufacturing of next-generation immune stimulating complexes - Ivan S. Pires; Kaiyuan Ni; Mariane Bandeira Melo; Na Li; Elana Ben-Akiva; Laura Maiorino; Jonathan Dye; Kristen A. Rodrigues; DongSoo Yun; Byungji Kim; Ryan R. Hosn; Paula T. Hammond; et al. (Chemical Engineering Journal, 2023)

Colchicine reduces the activation of NLRP3 inflammasome in COVID-19 patients - N. B. Amaral; T. S. Rodrigues; M. C. Giannini; M. I. Lopes; L. P. Bonjorno; P. I. S. O. Menezes; S. M. Dib; S. L. G. Gigante; M. N. Benatti; U. C. Rezek; L. L. Emrich-Filho; B. A. Sousa; et al. (Inflammation Research, 2023)

Oral formulation of Wnt inhibitor complex reduces inflammation and fibrosis in intraperitoneal implants in vivo - Ana Luíza de Castro Santos; Natália Jordana Alves da Silva; Celso Tarso Rodrigues Viana; Letícia Cristine Cardoso dos Santos; Gabriel Henrique Costa da Silva; Sérgio Ricardo Aluotto Scalzo Júnior; Pedro Augusto Carvalho Costa; Walison Nunes da Silva; Itamar Couto Guedes de Jesus; Alexander Birbrair; Mariana T. Q. de Magalhães; Frédéric Frézard; et al. (Drug Delivery and Translational Research, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Unveiling the membrane bound dihydroorotate: Quinone oxidoreductase from Staphylococcus aureus - Filipe M. Sousa; Patrícia Pires; Andreia Barreto; Patrícia N. Refojo; Micael S. Silva; Pedro B. Fernandes; Ana P. Carapeto; Tiago T. Robalo; Mário S. Rodrigues; Mariana G. Pinho; Eurico J. Cabrita; Manuela M. Pereira (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2023)

Acute bouts of aerobic and resistance exercise similarly alter inhibitory control and response time while inversely modifying plasma BDNF concentrations in middle-aged and older adults with type 2 diabetes - João G. Silveira-Rodrigues; Bruno T. Campos; André T. de Lima; Pedro H. M. Ogando; Camila B. Gomes; Patrícia F. Gomes; Ivana M. S. Aleixo; Danusa D. Soares (Experimental Brain Research, 2023)

Impact of climate changes in the suitable areas for Coffea arabica L. production in Mozambique: Agroforestry as an alternative management system to strengthen crop sustainability - Crimildo T. Cassamo; David Draper; Maria M. Romeiras; Isabel Marques; Rogério Chiulele; Marisa Rodrigues; Marc Stalmans; Fábio L. Partelli; Ana Ribeiro-Barros; José C. Ramalho (Agriculture, Ecosystems & Environment, 2023)

Four diterpenes identified in silico were isolated from Hyptidinae and demonstrated in vitro activity against Mycobacterium tuberculosis - Andreza Barbosa Silva Cavalcanti; Mayara dos Santos Maia; Pedro Thiago Ramalho de Figueiredo; Renata Priscila Barros de Menezes; Alex France Messias Monteiro; Roseana Araújo Ramos Meireles; Gabriela Cristina Soares Rodrigues; Ana Rita Rodrigues de Almeida Silva; Jociano da Silva Lins; Laísa Vilar Cordeiro; Valnês S. Rodrigues Junior; Ana Paula O. T. Castelo Branco; et al. (Natural Product Research, 2023)

Distribution and structural characterization of Balanites aegyptiaca (L.) Delile and Ricinodendron heudelotii (Bail.) Pierre among phytodistricts and land use types in Benin (West Africa) - Guillaume Hounsou-Dindin; Rodrigue Idohou; Marcel T. Donou Hounsode; Aristide Cossi Adomou; Achille Ephrem Assogbadjo; Romain Glèlè Kakaï (Tropical Ecology, 2023)

Correction to: The Role of Vicariance and Paleoclimatic Shifts in the Diversification of Uranoscodon superciliosus (Squamata, Tropiduridae) of the Amazonian Floodplains - Manuela V. dos Santos; Ana L. C. Prudente; Miguel T. Rodrigues; Marcelo J. Sturaro (Evolutionary Biology, 2023)

Pre-assessments of plant conservation status in islands: the case of French Overseas Territories - S. Véron; A. Bernard; E. Lebreton; C. Rodrigues-Vaz; M. Durand; L. Procopio; M. Hélion; M. Gayot; G. Viscardi; G. A. Krupnick; C. M. S. Carrington; V. Boullet; et al. (Biodiversity and Conservation, 2023)

Brazil fosters fossil fuel exploitation despite climate crises and the environmental vulnerabilities - Paulo Horta; Marina Sissini; Carolina Melissa Mueller; Fernanda M.M. Soares; Paulo Pagliosa; Leonardo Rörig; José Bonomi-Barufi; Flavio Berchez; Leticia Cotrim da Cunha; Rodrigo Kerr; Sergio Rossi; Marcelo O. Soares; et al. (Marine Policy, 2023)

Endotoxin tolerance and low activation of TLR-4/NF-κB axis in monocytes of COVID-19 patients - Gilson P. Dorneles; Paula C. Teixeira; Alessandra Peres; Luiz Carlos Rodrigues Júnior; Simone Gonçalves da Fonseca; Marta Chagas Monteiro; Sarah Eller; Tiago F. Oliveira; Eliana M. Wendland; Pedro R. T. Romão (Journal of Molecular Medicine, 2023)

Are mercury levels in fishery products appropriate to ensure low risk to high fish-consumption populations? - Elsa T. Rodrigues; João P. Coelho; Eduarda Pereira; Miguel A. Pardal (Marine Pollution Bulletin, 2023)

Improving the accuracy of beef cattle methane inventories in Latin America and Caribbean countries - Guilhermo F.S. Congio; André Bannink; Olga L. Mayorga; João P.P. Rodrigues; Adeline Bougouin; Ermias Kebreab; Paulo C.F. Carvalho; Telma T. Berchielli; Maria E.Z. Mercadante; Sebastião C. Valadares-Filho; Ana L.C.C. Borges; Alexandre Berndt; et al. (Science of The Total Environment, 2023)

Mouse organoids as an in vitro tool to study the in vivo intestinal response to cytotoxicants - F. Jardi; C. Kelly; C. Teague; H. Fowler-Williams; D. C. Sevin; D. Rodrigues; H. Jo; S. Ferreira; B. Herpers; M. Van Heerden; T. de Kok; C. Pin; et al. (Archives of Toxicology, 2023)

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Diversification of the Pristimantis conspicillatus group (Anura: Craugastoridae) within distinct neotropical areas throughout the Neogene - Antoine Fouquet; Alexandre Réjaud; Miguel T. Rodrigues; Santiago R. Ron; Juan C. Chaparro; Mariela Osorno; Fernanda P. Werneck; Tomas Hrbek; Albertina P. Lima; Teresa Camacho-Badani; Andres F. Jaramillo-Martinez; Jérôme Chave (Systematics and Biodiversity, 2022)

Species diversity and systematics of the Leptodactylus melanonotus group (Anura, Leptodactylidae): review of diagnostic traits and a new species from the Eastern Guiana Shield - Thiago R. Carvalho; Antoine Fouquet; Mariana L. Lyra; Ariovaldo A. Giaretta; C. Eduardo Costa-Campos; Miguel T. Rodrigues; Célio F. B. Haddad; Santiago R. Ron (Systematics and Biodiversity, 2022)

Environmental disaster in mining areas: routes of exposure to metals in the Doce River basin - A. R. de Matos; H. T. da Silva; M. C. S. da Faria; B. M. Freire; R. M. Pereira; B. L. Batista; J. L. Rodrigues (International Journal of Environmental Science and Technology, 2022)

The Role of Vicariance and Paleoclimatic Shifts in the Diversification of Uranoscodon superciliosus (Squamata, Tropiduridae) of the Amazonian Floodplains - Manuela V. dos Santos; Ana L. C. Prudente; Miguel T. Rodrigues; Marcelo J. Sturaro (Evolutionary Biology, 2022)

Cerrado deforestation threatens regional climate and water availability for agriculture and ecosystems - Ariane A. Rodrigues; Marcia N. Macedo; Divino V. Silvério; Leandro Maracahipes; Michael T. Coe; Paulo M. Brando; Julia Z. Shimbo; Raoni Rajão; Britaldo Soares‐Filho; Mercedes M. C. Bustamante (Global Change Biology, 2022)
The Brazilian Cerrado is one of the most biodiverse savannas in the world, yet 46% of its original cover has been cleared to make way for crops and pastures. These extensive land‐use transitions (LUTs) are expected to influence regional climate by reducing evapotranspiration (ET), increasing land surface temperature (LST), and ultimately reducing precipitation. Here, we quantify the impacts of LUTs on ET and LST in the Cerrado by combining MODIS satellite data with annual land use and land cover maps from 2006 to 2019. We performed regression analyses to quantify the effects of six common LUTs on ET and LST across the entire gradient of Cerrado landscapes. Results indicate that clearing forests for cropland or pasture increased average LST by ~3.5°C and reduced mean annual ET by 44% and 39%, respectively. Transitions from woody savannas to cropland or pasture increased average LST by 1.9°C and reduced mean annual ET by 27% and 21%, respectively. Converting native grasslands to cropland or pasture increased average LST by 0.9 and 0.6°C, respectively. Conversely, grassland‐to‐pasture transitions increased mean annual ET by 15%. To date, land changes have caused a 10% reduction in water recycled to the atmosphere annually and a 0.9°C increase in average LST across the biome, compared to the historic baseline under native vegetation. Global climate changes from increased atmospheric greenhouse gas concentrations will only exacerbate these effects. Considering potential future scenarios, we found that abandoning deforestation control policies or allowing legal deforestation to continue (at least 28.4 Mha) would further reduce yearly ET (by −9% and −3%, respectively) and increase average LST (by +0.7 and +0.3°C, respectively) by 2050. In contrast, policies encouraging zero deforestation and restoration of the 5.2 Mha of illegally deforested areas would partially offset the warming and drying impacts of land‐use change.

Corrigendum to the paper: Reassessing the systematics of Leptodeira (Serpentes, Dipsadidae) with emphasis in the South American species - João C. L. Costa; Roberta Graboski; Felipe G. Grazziotin; Hussam Zaher; Miguel T. Rodrigues; Ana Lúcia da C. Prudente (Zoologica Scripta, 2022)

Reassessing the systematics of Leptodeira (Serpentes, Dipsadidae) with emphasis in the South American species - João C. L. Costa; Roberta Graboski; Felipe G. Grazziotin; Hussam Zaher; Miguel T. Rodrigues; Ana Lúcia da C. Prudente (Zoologica Scripta, 2022)
Within the diverse subfamily Dipsadinae, Imantodini represents one of the few groups distributed in North, Central and South America. The tribe comprises the genera Leptodeira and Imantodes , from which Leptodeira is the most diverse, including 15 species and 11 subspecies, distributed from southern USA to central Argentina. Taxonomy and affinities among these taxa are poorly resolved, and the phylogenetic relationships among the South American diversity were never properly assessed before. Here, we investigate the phylogenetic relationships and the taxonomic status of Leptodeira spp. based on a comprehensive multilocus dataset with emphasis in the South American radiation. Besides assessing the phylogenetic relationship and species cohesion, we also evaluate the morphological variation among the South American diversity of Leptodeira . Our results support the monophyly of Imatodini and Leptodeira , while indicating that several individuals classified as Leptodeira annulata and L . septentrionalis do not cluster together within their respective species. Moreover, specimens identified as belonging to the subspecies L . a . annulata , L . a . cussiliris , L . s . ornata and L . s . polysticta do not group together suggesting the current classification includes non‐natural groups. The analysis of morphological evidence also supports the phylogenetics results, indicating that several clades can be recognized as evolutionary units presenting distinct phenotypes. To equate the taxonomy to our results, we propose a new taxonomic arrangement for Leptodeira in which we are: (1) redefining the composition of L . annulata and L . septentrionalis ; (2) elevating five subspecies to species level; (3) revalidating one species; (4) recognizing four species complexes; and (5) indicating the presence of hidden diversity (probably four undescribed species). Finally, we describe a new species ( Leptodeira tarairiu sp. nov.) from the open formations of South America (Cerrado and Caatinga), and we provide detailed redescriptions for all South American species of Leptodeira .

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Optical time series for the separation of land cover types with similar spectral signatures: cocoa agroforest and forest - João E. Batista; Nuno M. Rodrigues; Ana I. R. Cabral; Maria J. P. Vasconcelos; Adriano Venturieri; Luiz G. T. Silva; Sara Silva (International Journal of Remote Sensing, 2022)

Correction to: Basic oxygen furnace sludge to treat industrial arsenic- and sulfate‑rich acid mine drainage - Sandrine F. Araujo; Cláudia L. Caldeira; Virginia S. T. Ciminelli; Ricardo P. Borba; Joanna P. Rodrigues; Gustavo F. Simões (Environmental Science and Pollution Research, 2022)

Basic oxygen furnace sludge to treat industrial arsenic- and sulfate-rich acid mine drainage - Sandrine F. Araujo; Cláudia L. Caldeira; Virginia S. T. Ciminelli; Ricardo P. Borba; Joanna P. Rodrigues; Gustavo F. Simões (Environmental Science and Pollution Research, 2022)

Correction to: Lettuce (Lactuca sativa L.) germplasm resistant to bacterial leaf spot caused by race 1 of Xanthomonas hortorum pv. vitians (Brown 1918) Morinière et al. 2020 - Germán V. Sandoya; Emma Rosenthal; Ivan Simko; Lis N. Rodrigues-Porto; William H. Wadlington; Carolee T. Bull; Amanda Carroll (Journal of Plant Pathology, 2022)

Lettuce (Lactuca sativa L.) germplasm resistant to bacterial leaf spot caused by race 1 of Xanthomonas hortorum pv. vitians (Brown 1918) Morinière et al. 2020 - Germán V. Sandoya; Emma Rosenthal; Ivan Simko; Lis N. Rodrigues-Porto; William H. Wadlington; Carolee T. Bull; Amanda Carroll (Journal of Plant Pathology, 2022)

Folic acid supplementation during pregnancy alters behavior in male rat offspring: nitrative stress and neuroinflammatory implications - Josiane Silva Silveira; Osmar Vieira Ramires Júnior; Felipe Schmitz; Fernanda Silva Ferreira; Fabiana Cristina Rodrigues; Robson Coutinho Silva; Luiz Eduardo Baggio Savio; Angela T. S. Wyse (Molecular Neurobiology, 2022)

Onset and demise dates of the rainy season in the South American monsoon region: A cluster analysis result - Maria A. M. Rodrigues; Sâmia R. Garcia; Mary T. Kayano; Alan J. P. Calheiros; Rita V. Andreoli (International Journal of Climatology, 2022)
This work proposes an adaptation of the method developed in previous papers to determine the onset and demise of the rainy season (ONR and DER) dates in the areas of the South American monsoon system (SAMS) based on the pentad antisymmetric outgoing long‐wave radiation (AOLR). In those papers, the sign change of the mean AOLR in the central Amazon Basin (CAM) and western central Brazil (WCB) from positive to negative defined the ONR, from negative to positive, the DER dates. Since the monsoon convection presents a northwest–southeast oriented progression, the antisymmetric area to the WCB was selected subjectively. Thus, here we propose to use the Ward hierarchical clustering method to select areas in the SAMS and in the northern tropical America (NTA) for the regionalized AOLR calculation. The significant (at the 95% confidence level) negative correlations with the largest magnitude among the clusters in the SAMS and NTA and the outgoing long‐wave radiation (OLR) and precipitation annual cycles in each group define the pairs to calculate the AOLR. Then, the AOLR time series is calculated and subjected to a 5‐pentad running mean filter. This method keeps the climatological features of the convection annual cycle such that the closer (farther) the pair is to the equator the longer (shorter) the rainy season. The ONR and DER dates found with this new method are remarkably close to those found previously. Therefore, the new method proposed here highlights regional aspects of rainy season and can easily be automatized for its routine application at the operational climate monitoring centres, for instance at INPE. This is the most important advantage of the method and might be relevant to the SAMS rainy season monitoring.

Role of the YehD fimbriae in the virulence‐associated properties of enteroaggregative Escherichia coli - Jorge Soria‐Bustos; Waleska Saitz; Abraham Medrano; Cristina Lara‐Ochoa; Zineb Bennis; Valerio Monteiro‐Neto; Camilla Itapary dos Santos; Josias Rodrigues; Rodrigo T. Hernandes; Jorge A. Yáñez; Javier Torres; Fernando Navarro‐García; et al. (Environmental Microbiology, 2022)
Summary The interaction of enteroaggregative Escherichia coli (EAEC) strains with the colonic gut mucosa is characterized by the ability of the bacteria to form robust biofilms, to bind mucin, and induce a local inflammatory response. These events are mediated by a repertoire of five different aggregative adherence fimbriae variants (AAF/I‐V) typically encoded on virulence plasmids. In this study, we report the production in EAEC strains of a new Y eh D f imbriae (YDF), which is encoded by the chromosomal gene cluster yehABCD , also present in most E. coli strains. Immuno‐labelling of EAEC strain 042 with anti‐AAF/II and anti‐YDF antibodies demonstrated the presence of both AAF/II and YDF on the bacterial surface. We investigated the role of YDF in cell adherence, biofilm formation, colonization of spinach leaves, and induction of pro‐inflammatory cytokines release. To this aim, we constructed yehD deletion mutants in different EAEC backgrounds (strains 17‐2, 042, 55989, C1010, 278‐1, J7) each harbouring one of the five AAFs. The effect of the YDF mutation was strain dependent and AAF independent as the lack of YDF had a different impact on the phenotypes manifested by the different EAECs tested. Expression of the yehABCD operon in a E. coli K12 ORN172 showed that YDF is important for biofilm formation but not for adherence to HeLa cells. Lastly, screening of pro‐inflammatory cytokines in supernatants of Caco‐2 cells infected with EAEC strains 042 and J7 and their isogenic Δ yehD mutants showed that these mutants were significantly defective in release of IL‐8 and TNF‐α. This study contributes to the understanding of the complex and diverse mechanisms of adherence of EAEC strains and identifies a new potential target for preventive measures of gastrointestinal illness caused by EAEC and other E. coli pathogroups.

Pharmacological blockage of the AHR-CYP1A1 axis: a call for in vivo evidence - N. R. Coelho; A. B. Pimpão; M. J. Correia; T. C. Rodrigues; E. C. Monteiro; J. Morello; S. A. Pereira (Journal of Molecular Medicine, 2022)

Prospecting for a quinoline containing selenium for comorbidities depression and memory impairment induced by restriction stress in mice - Renata L. de Oliveira; Guilherme T. Voss; Karline da C. Rodrigues; Mikaela P. Pinz; Julia V. Biondi; Nicole P. Becker; Eduardo Blodorn; William B. Domingues; Allya Larroza; Vinícius F. Campos; Diego Alves; Ethel A. Wilhelm; et al. (Psychopharmacology, 2022)

Spatial controls on riverbed sediment chemistry in three anthropogenically modified tropical mountainous watersheds - J. Papotto; L. J. Rodrigues; E. M. Siebert; E. J. Wagner; S. T. Goldsmith (International Journal of Environmental Science and Technology, 2022)

Surface functionalization of natural hydroxyapatite by polymerization of β-cyclodextrin: application as electrode material for the electrochemical detection of Pb(II) - Rodrigue Tchoffo; Guy B. P. Ngassa; Giscard Doungmo; Arnaud T. Kamdem; Ignas K. Tonlé; Emmanuel Ngameni (Environmental Science and Pollution Research, 2022)

Pyramiding dsRNAs increases phytonematode tolerance in cotton plants - Maria E. Lisei-de-Sá; Paolo L. Rodrigues-Silva; Carolina V. Morgante; Bruno Paes de Melo; Isabela T. Lourenço-Tessutti; Fabricio B. M. Arraes; João P. A. Sousa; Rafael Galbieri; Regina M. S. Amorim; Camila B. J. de Lins; Leonardo L. P. Macedo; Valdeir J. Moreira; et al. (Planta, 2021)

Production and bioaccessibility of Emiliania huxleyi biomass and bioactivity of its aqueous and ethanolic extracts - B. Vicente; J. Matos; R. Gomes; M. Sapatinha; Cláudia Afonso; T. Rodrigues; A. Amorim; N. M. Bandarra; Carlos Cardoso (Journal of Applied Phycology, 2021)

Determination of intestinal absorption of the paralytic shellfish toxin GTX-5 using the Caco-2 human cell model - Elsa T. Rodrigues; Susana F. Nascimento; Cristiana L. Pires; Lia P. Godinho; Catarina Churro; Maria João Moreno; Miguel A. Pardal (Environmental Science and Pollution Research, 2021)

Whiptail lizard lineage delimitation and population expansion as windows into the history of Amazonian open ecosystems - Lidia F. Martins; Erik L. Choueri; Alan F. S. Oliveira; Fabrícius M. C. B. Domingos; Gabriel H. O. Caetano; Vitor H. G. L. Cavalcante; Rafael N. Leite; Antoine Fouquet; Miguel T. Rodrigues; Ana C. Carnaval; Guarino R. Colli; Fernanda P. Werneck (Systematics and Biodiversity, 2021)

Toxicity Assays of Commercial Chlorpyrifos Under UV/H2O2 and UVC Photolysis Treatments - Suelen Angeli; Eliane Adams; Gabriella P. Masceno; Rúbia M. Lima; Larisa M. Utzig; Fernando Rodrigues-Silva; Liziê D. T. Prola; Adriane M. Freitas; Marcus V. Liz (Water, Air, & Soil Pollution, 2021)

Tropical grass and legume pastures may alter lamb meat physical and chemical characteristics - V. S. Hampel; C. H. E. C. Poli; M. Joy; J. F. Tontini; T. Devincenzi; J. R. B. Pardos; R. E. F. Macedo; E. N. Nalério; A. G. F. Saccol; E. Rodrigues; V. Manfroi; N. M. Fajardo (Tropical Animal Health and Production, 2021)

Exhumation of an anatectic complex by channel flow and extrusion tectonics: structural and metamorphic evidence from the Porto–Viseu Metamorphic Belt, Central-Iberian Zone - T. Bento dos Santos; J. F. Rodrigues; P. Castro; B. Cotrim; I. Pereira; J. A. Ferreira; C. Meireles; N. Ferreira; P. Ferreira; A. Ribeiro; F. Guimarães (International Journal of Earth Sciences, 2021)

Soybean seed chemical treatment associated with inoculants: physiological and agronomical analyses - V. M. Santos; T. C. Oliveira; M. G. Mendes; C. H. Yamanaka; Willian Rodrigues Macedo (Plant Physiology Reports, 2021)

KIR2DL4 genetic diversity in a Brazilian population sample: implications for transcription regulation and protein diversity in samples with different ancestry backgrounds - Emiliana Weiss; Heloisa S. Andrade; Juliana Rodrigues Lara; Andreia S. Souza; Michelle A. Paz; Thálitta H. A. Lima; Iane O. P. Porto; Nayane S. B. Silva; Camila F. Bannwart Castro; Rejane M. T. Grotto; Eduardo A. Donadi; Celso T. Mendes-Junior; et al. (Immunogenetics, 2021)

Peptide fraction from latex of Calotropis procera exhibits antifungal and insecticidal activities - Jackson L. Amaral; Cleverson D. T. Freitas; João P. V. Rodrigues; Ghulam Hussain; Márcio V. Ramos; Pedro F. N. Souza (Arthropod-Plant Interactions, 2021)

Environmental correlates of taxonomic and phylogenetic diversity in the Atlantic Forest - Andrea Paz; Jason L. Brown; Carlos L. O. Cordeiro; Julian Aguirre‐Santoro; Claydson Assis; Renata Cecilia Amaro; Fabio Raposo do Amaral; Thuane Bochorny; Lucas F. Bacci; Mayara K. Caddah; Fernando d’Horta; Miriam Kaehler; et al. (Journal of Biogeography, 2021)
Aim There is little consensus on which environmental variables are best at predicting multiple dimensions of diversity. We ask whether there are common environmental correlates of diversity, despite ecological differences, across nine clades of plants and animals distributed along a single rainforest domain. For that, we compare the environmental correlates of species richness, phylogenetic diversity, and phylogenetic endemism. Location Brazilian Atlantic Forest. Taxon: Five clades of plants (Bromelioideae, Miconieae, Bertolonia , Cambessedesieae, and the Fridericia and allies) and four clades of animals (butterlies in the tribe Ithomiini, frogs in the genera Boana and Proceratophrys , and birds in the subfamily Thraupinae). Methods Using curated occurrence localities and phylogenetic data, we generated maps of (a) species richness, (b) phylogenetic diversity, (c) residuals of phylogenetic diversity regressed on species richness, and (d) phylogenetic endemism for all groups. We also compiled a set of 30 environmental descriptors, including records of current temperature and precipitation, climatic stability over time, and topography. Through a machine learning framework, we explored the environmental correlates of each of these diversity measures for each group. Results The environmental variables used here were strong predictors of diversity for all studied groups. However, models for phylogenetic endemism had lower predictive power. Although patterns of diversity are different among groups, correlates of diversity are consistent across taxa. For both species richness and phylogenetic diversity, current precipitation and precipitation stability over time were consistently ranked among the variables that strongly correlate with diversity patterns. The correlates of phylogenetic endemism were less homogeneous across groups. The results suggest that including climate stability over time is important when predicting diversity measures that reflect historical components. Main conclusions Investigating environmental correlates of diversity for multiple clades and diversity measures in a single geographic area allows for a better understanding of common patterns across taxa. This study shows that environmental conditions, particularly precipitation, are good predictors of the patterns of species richness and phylogenetic diversity‐but not phylogenetic endemism‐across different Atlantic Forest groups.

Systematics and biogeography of the Boana albopunctata species group (Anura, Hylidae), with the description of two new species from Amazonia - Antoine Fouquet; Pedro Marinho; Alexandre Réjaud; Thiago R. Carvalho; Marcel A. Caminer; Martin Jansen; Raíssa N. Rainha; Miguel T. Rodrigues; Fernanda P. Werneck; Albertina P. Lima; Tomas Hrbek; Ariovaldo A. Giaretta; et al. (Systematics and Biodiversity, 2021)

Genomic data from the Brazilian sibilator frog reveal contrasting pleistocene dynamics and regionalism in two South American dry biomes - Maria Tereza C. Thomé; Bryan C. Carstens; Miguel T. Rodrigues; João Alexandrino; Célio F. B. Haddad (Journal of Biogeography, 2021)
Aim Knowledge about the Neotropical dry formations, particularly the Caatinga, remains rudimentary compared to other biotas in the region. Here we address several biogeographical hypotheses by combining intense geographical and genomic sampling obtained for the Brazilian sibilator frog. We specifically test predictions related to the putative roles of past climate shifts (Pleistocene and Holocene) and local geographical barriers (past and current courses of the São Francisco River, SFR) in causing population differentiation in this species. Location Caatinga and eastern Cerrado. Taxon Brazilian sibilator frog Leptodactylus troglodytes . Methods We sequenced up to ~15,000 single nucleotide polymorphisms for 159 samples from 61 locations. We inferred genetic structure using spatial clustering and examined population sizes through time. We estimated the relationship among populations using phylogenetic reconstruction, estimated historical distributions with ecological niche modelling and inferred demographic history under isolation‐with‐migration models. Results Genetic diversity in L. troglodytes corresponds to biome boundaries, with one population in the Cerrado and two populations in the Caatinga, separated by the SFR. Demographic model selection indicates the Caatinga populations expanded since the end of the Pleistocene while the Cerrado population declined. Within the Caatinga, population expansion began earlier and was more extreme in the north. A continuous stability area maintained the two Caatinga populations, which share a common origin and began diverging in the mid‐Pleistocene, first with symmetric gene flow and later under pronounced migration from the north. Main conclusions We could not reject a role of past climate change in causing diversification of relictual populations in the Cerrado, but we found no evidence of multiple refuges or long‐term isolation within the Caatinga. Instead, diversification in this biome appears to be caused by the SFR acting as a ‘soft barrier’ that constrains migration over an extended period of time.

Scale‐dependent patterns of metacommunity structuring in aquatic organisms across floodplain systems - Fernando M. Lansac‐Tôha; Luis M. Bini; Jani Heino; Bianca R. Meira; Bianca T. Segovia; Carla S. Pavanelli; Claudia C. Bonecker; Claudia P. de Deus; Evanilde Benedito; Geziele M. Alves; Gislaine I. Manetta; Juliana D. Dias; et al. (Journal of Biogeography, 2021)
Aim Evaluating how groups of organisms vary in dispersal capability and how environmental, spatial and temporal signals vary across multiple scales is critical to elucidating metacommunity theory. We examined whether the relative contributions of environmental, spatial and hydrological factors have different effects on organismal groups with different dispersal abilities at three spatial scales, and how this knowledge contributes to our understanding of metacommunity dynamics. Location Four major Brazilian floodplains, with the largest distance among them of 2,300 Km. Taxon 10 aquatic organismal groups, ranging from bacterioplankton to fish. Methods We sampled lakes connected to the main river in the low‐ and high‐water periods of each floodplain between 2011 and 2012. Different biological groups were analysed across three hierarchical spatial scales (fine, intermediate and subcontinental) within and between floodplain systems. We applied a series of partial redundancy analyses to estimate the relative contributions of environmental factors, spatial factors and hydrological period for each biological group. Results At the fine spatial scale, predominantly environmental factors and hydrological period structure metacommunities, although less so for microorganisms than for micro‐invertebrates and macro‐organisms. The relative importance of environmental factors increased at the intermediate spatial scale. At the subcontinental scale, the relative importance of spatial factors increased for all biological groups, but environmental factors remained the primary regulators of microorganisms even at the largest scale. Main conclusions This study design allowed us to make more robust inferences about the mechanisms responsible for regulating community structure of distinct biological groups at different spatial scales. Our results suggest that biological groups displaying distinct body size likely determine the spatial extent at which environmental, spatial and hydrological processes prevail as the primary regulators of community structure. These findings are important in guiding the conservation and management of floodplain biodiversity because these systems are naturally highly heterogeneous in space and time.

Seasonal variation in photosynthetic rates and satellite-based GPP estimation over mangrove forest - N. Lele; M. K. Kripa; M. Panda; S. K. Das; A. Hari Nivas; N. Divakaran; S. Naik-Gaonkar; A. Sawant; A. K. Pattnaik; R. N. Samal; T. Thangaradjou; A. Saravanakumar; et al. (Environmental Monitoring and Assessment, 2021)

Violacein antimicrobial activity on Staphylococcus epidermidis biofilm - H. V. Dodou; A. H. M. Batista; S. C. Medeiros; G. W. P. Sales; M. L. Rodrigues; P. I. O. Pereira; P. C. N. Nogueira; E. R. Silveira; T. B. Grangeiro; N. A. P. Nogueira (Natural Product Research, 2020)

Recent advances on anaerobic digestion of swine wastewater - G. Lourinho; L. F. T. G. Rodrigues; P. S. D. Brito (International Journal of Environmental Science and Technology, 2020)

Historical biogeography identifies a possible role of Miocene wetlands in the diversification of the Amazonian rocket frogs (Aromobatidae: Allobates ) - Alexandre Réjaud; Miguel T. Rodrigues; Andrew J. Crawford; Santiago Castroviejo‐Fisher; Andrés F. Jaramillo; Juan C. Chaparro; Frank Glaw; Giussepe Gagliardi‐Urrutia; Jiří Moravec; Ignacio J. De la Riva; Pedro Perez; Albertina P. Lima; et al. (Journal of Biogeography, 2020)
Aim We investigate the spatiotemporal context of the diversification of Allobates , a widespread genus of Amazonian frogs with high species diversity particularly in western Amazonia. We tested if that diversity originated in situ or through repeated dispersals from other Amazonian areas and if this diversification took place during or after the Pebas system, a vast lacustrine system occupying most western Amazonia between 23 and 10 million years ago (Mya). Location Amazonia. Taxon Allobates (Anura: Aromobatidae). Methods We gathered a spatially and taxonomically extensive sampling of mitochondrial DNA sequences from 932 Allobates specimens to delimit Operational Taxonomic Units (OTUs). Complete mitogenomes of these OTUs were assembled to reconstruct a time‐calibrated phylogeny used to infer the historical and spatial origin of the Amazonian Allobates lineages. Results Phylogenetic analyses and ancestral area reconstruction suggested that most of the western Amazonian lineages resulted from in situ diversification and that these events occurred between the inferred origin of the genus (25 Mya) and 10 Mya, with a possible peak between 14 and 10 Mya. Dispersal among areas mostly occurred from western Amazonia towards the Brazilian and the Guiana Shields. Closely related Allobates OTUs display an allopatric pattern of distribution, matching interfluves delimited by modern Amazonian rivers. Main Conclusions In western Amazonia, diversification of Allobates appears to have been simultaneous with the last stages of the Pebas system (14–10 Mya). Subsequently (within the last 10 Mya), modern Amazonian river courses shaped the distribution pattern of Allobates species and possibly promoted allopatric speciation.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Spatial distribution of the level of return of extreme precipitation events in Northeast Brazil - Daniele T. Rodrigues; Weber A. Gonçalves; Maria H. C. Spyrides; Cláudio M. Santos e Silva; Diego O. de Souza (International Journal of Climatology, 2020)
This study aimed to estimate levels of return of extreme daily precipitation events, associating them with natural disasters in Northeast Brazil (NEB), a region characterized by different climatic conditions and low rates of social and economic development. For this, generalized Pareto distribution (GPD) models were adjusted to the daily extreme precipitation data estimated by the Tropical Rainfall Measuring Mission (TRMM) 3B42 product of the multisatellite precipitation analysis for a period of 16 years (2000–2015). In addition, the estimates of the GPD model were compared using two data sources, TRMM and pluviometer. The investigation showed that the results of the GPD model estimated by means of the extreme data from the rain gauge and the TRMM were statistically the same, with 95% confidence. Thus, using the data referring to the 2,082 grid points of the TRMM, it was possible to map the spatial distribution of the estimates of the levels of return of extreme precipitation to the return periods of 2, 5 and 10 years, per seasonal period. In general, the results indicated that the intensity of expected extreme precipitation depends on the seasonal period and the place of occurrence of precipitation. The eastern NEB stood out as the region where the highest intensities of extreme precipitation are expected. Extreme precipitation values of up to 178 mm are expected in 2 years. The areas where natural disasters occurred in the years 2016, 2017 and 2018 are similar to those in which the highest rainfall intensities are expected. The results of this study can allow the evaluation of the spatial distribution of risks related to extreme precipitation events, and therefore, support the planning of regional public policies and environmental management for the prevention of natural disasters in NEB.

SERK genes identification and expression analysis during somatic embryogenesis and sporogenesis of sexual and apomictic Brachiaria brizantha (Syn. Urochloa brizantha) - Andréa D. Koehler; André S. T. Irsigler; Vera T. C. Carneiro; Glaucia B. Cabral; Júlio C. M. Rodrigues; Ana Cristina M. M. Gomes; Roberto C. Togawa; Marcos M. C. Costa; Adriana Pinheiro Martinelli; Diva Maria de Alencar Dusi (Planta, 2020)

Retrospective study of porcine circovirus 3 (PCV3) in swine tissue from Brazil (1967–2018) - I. L. F. Rodrigues; A. C. M. Cruz; A. E. Souza; F. B. Knackfuss; C. H. C. Costa; R. L. Silveira; T. X. Castro (Brazilian Journal of Microbiology, 2020)

Entomopathogenic Viruses in the Neotropics: Current Status and Recently Discovered Species - D R Sosa-Gómez; F S Morgado; R F T Corrêa; L A Silva; D M P Ardisson-Araújo; B M P Rodrigues; E E Oliveira; R W S Aguiar; B M Ribeiro (Neotropical Entomology, 2020)

Correction to: CpG‑creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)

CpG-creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)
Mutations can occur throughout the virus genome and may be beneficial, neutral or deleterious. We are interested in mutations that yield a C next to a G, producing CpG sites. CpG sites are rare in eukaryotic and viral genomes. For the eukaryotes, it is thought that CpG sites are rare because they are prone to mutation when methylated. In viruses, we know less about why CpG sites are rare. A previous study in HIV suggested that CpG-creating transition mutations are more costly than similar non-CpG-creating mutations. To determine if this is the case in other viruses, we analyzed the allele frequencies of CpG-creating and non-CpG-creating mutations across various strains, subtypes, and genes of viruses using existing data obtained from Genbank, HIV Databases, and Virus Pathogen Resource. Our results suggest that CpG sites are indeed costly for most viruses. By understanding the cost of CpG sites, we can obtain further insights into the evolution and adaptation of viruses.

Correction to: In vitro mechanistic studies on α-amanitin and its putative antidotes - Daniela Ferreira Rodrigues; Ricardo Pires das Neves; Alexandra T. P. Carvalho; Maria Lourdes Bastos; Vera M. Costa; Félix Carvalho (Archives of Toxicology, 2020)

In vitro mechanistic studies on α-amanitin and its putative antidotes - Daniela Ferreira Rodrigues; Ricardo Pires das Neves; Alexandra T. P. Carvalho; Maria Lourdes Bastos; Vera M. Costa; Félix Carvalho (Archives of Toxicology, 2020)

Gold-Coated Superparamagnetic Iron Oxide Nanoparticles Attenuate Collagen-Induced Arthritis after Magnetic Targeting - Maria Fernanda Hornos Carneiro; Ana Rita T. Machado; Lusânia M. G. Antunes; Talita E. Souza; Victor A. Freitas; Luiz C. A. Oliveira; Jairo L. Rodrigues; Marcio C. Pereira; Fernando Barbosa (Biological Trace Element Research, 2020)

Evidence of strong population bottleneck in genetics of endangered Brazilian Merganser (Mergus octosetaceus) - T. A. Maia; D. P. Campos; L. R. Silva; L. V. Lins; F. Ribeiro; F. Sebaio; F. R. Rodrigues; G. P. M. Dantas (Journal of Ornithology, 2020)

Cell-based assays as an alternative for the study of aquatic toxicity of pharmaceuticals - Elsa T. Rodrigues; Ana T. Varela; Miguel A. Pardal; Vilma A. Sardão (Environmental Science and Pollution Research, 2020)

Rain forest shifts through time and riverine barriers shaped the diversification of South American terrestrial pit vipers ( Bothrops jararacussu species group) - Francisco Dal Vechio; Ivan Prates; Felipe G. Grazziotin; Hussam Zaher; Roberta Graboski; Miguel T. Rodrigues (Journal of Biogeography, 2020)
Aim To investigate (a) historical biogeographical connections and species interchange among rain forest habitats and (b) the role of riverine barriers on population divergence and speciation in the Neotropical region. Location Amazonia and Atlantic Forest in South America. Taxon Bothrops jararacussu species group (Serpentes: Viperidae). Methods We inferred phylogenetic relationships within Bothrops with an emphasis on the jararacussu species group under a Bayesian framework based on six molecular loci. We also used genetic coalescent simulations and approximate Bayesian computation to infer historical demography within the jararacussu group based on tests of alternative scenarios. Results We found the jararacussu species group to be monophyletic. The Atlantic Forest species B. pirajai and B. muriciensis were inferred nested within this group, closely related to B. jararacussu , confirming that Atlantic Forest species form a clade. The historical demographic analyses support vicariant separation between populations of B. brazili north and south of the Amazon River during the Miocene–Pliocene border, as well as colonization of the Atlantic Forest by a northern Amazonian ancestor in the Pleistocene. Main Conclusion The evolutionary history of the jararacussu species group sheds light on the dynamism of Neotropical rain forests over time, with at least one event of forest expansion leading to faunal interchange between Amazonian and Atlantic forests in the Pleistocene. Moreover, tests of alternative demographic scenarios suggest that the populations of B. brazili from north and south of the Amazon River originated from a vicariant event during the Miocene–Pliocene border, in agreement with the proposed age of establishment of the modern Amazon River drainage. Our results also have taxonomic implications for these medically important venomous snakes, supporting unrecognized diversity at the species level.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

A novel homozygous RTEL1 variant in a consanguineous Lebanese family: phenotypic heterogeneity and disease anticipation - Fernanda Gutierrez-Rodrigues; Nohad Masri; Eliane Chouery; Carrie Diamond; Nadine Jalkh; Alana Vicente; Sachiko Kajigaya; Fayez Abillama; Noha Bejjani; Wassim Serhal; Rodrigo T. Calado; Neal S. Young; et al. (Human Genetics, 2019)

Testing main Amazonian rivers as barriers across time and space within widespread taxa - Renata M. Pirani; Fernanda P. Werneck; Andréa T. Thomaz; Mariah L. Kenney; Marcelo J. Sturaro; Teresa C. S. Ávila‐Pires; Pedro L. V. Peloso; Miguel T. Rodrigues; L. Lacey Knowles (Journal of Biogeography, 2019)
Aim Present Amazonian diversity patterns can result from many different mechanisms and, consequently, the factors contributing to divergence across regions and/or taxa may differ. Nevertheless, the river‐barrier hypothesis is still widely invoked as a causal process in divergence of Amazonian species. Here we use model‐based phylogeographic analyses to test the extent to which major Amazonian rivers act similarly as barriers across time and space in two broadly distributed Amazonian taxa. Local Amazon rain forest. Taxon The lizard Gonatodes humeralis (Sphaerodactylidae) and the tree frog Dendropsophus leucophyllatus (Hylidae). Methods We obtained RADseq data for samples distributed across main river barriers, representing main Areas of Endemism previously proposed for the region. We conduct model‐based phylogeographic and genetic differentiation analyses across each population pair. Results Measures of genetic differentiation (based on F ST calculated from genomic data) show that all rivers are associated with significant genetic differentiation. Parameters estimated under investigated divergence models showed that divergence times for populations separated by each of the 11 bordering rivers were all fairly recent. The degree of differentiation consistently varied between taxa and among rivers, which is not an artifact of any corresponding difference in the genetic diversities of the respective taxa, or to amounts of migration based on analyses of the site‐frequency spectrum. Main conclusions Taken together, our results support a dispersal (rather than vicariance) history, without strong evidence of congruence between these species and rivers. However, once a species crossed a river, populations separated by each and every river have remained isolated—in this sense, rivers act similarly as barriers to any further gene flow. This result suggests differing degrees of persistence and gives rise to the seeming contradiction that the divergence process indeed varies across time, space and species, even though major Amazonian rivers have acted as secondary barriers to gene flow in the focal taxa.

The environmental condition of an estuarine ecosystem disturbed by pesticides - Elsa T. Rodrigues; Maria Fátima Alpendurada; Ana Guimarães; Romeu Avó; Bárbara Ferreira; Miguel A. Pardal (Environmental Science and Pollution Research, 2019)

Early Interaction of Alternaria infectoria Conidia with Macrophages - M. C. Almeida; D. Antunes; B. M. A. Silva; L. Rodrigues; M. Mota; O. Borges; C. Fernandes; T. Gonçalves (Mycopathologia, 2019)

The Tropical Atlantic Observing System - G. R. Foltz; P. Brandt; I. Richter; B. Rodríguez-Fonseca; F. Hernandez; M. Dengler; R. R. Rodrigues; J. O. Schmidt; L. Yu; N. Lefevre; L. Cotrim Da Cunha; M. J. McPhaden; et al. (Frontiers in Marine Science, 2019)
The tropical Atlantic is home to multiple coupled climate variations covering a wide range of timescales and impacting societally relevant phenomena such as continental rainfall, Atlantic hurricane activity, oceanic biological productivity, and atmospheric circulation in the equatorial Pacific. The tropical Atlantic also connects the southern and northern branches of the Atlantic meridional overturning circulation and receives freshwater input from some of the world’s largest rivers. To address these diverse, unique, and interconnected research challenges, a rich network of ocean observations has developed, building on the backbone of the Prediction and Research Moored Array in the Tropical Atlantic (PIRATA). This network has evolved naturally over time and out of necessity in order to address the most important outstanding scientific questions and to improve predictions of tropical Atlantic severe weather and global climate variability and change. The tropical Atlantic observing system is motivated by goals to understand and better predict phenomena such as tropical Atlantic interannual to decadal variability and climate change; multidecadal variability and its links to the meridional overturning circulation; air-sea fluxes of CO 2 and their implications for the fate of anthropogenic CO 2 ; the Amazon River plume and its interactions with biogeochemistry, vertical mixing, and hurricanes; the highly productive eastern boundary and equatorial upwelling systems; and oceanic oxygen minimum zones, their impacts on biogeochemical cycles and marine ecosystems, and their feedbacks to climate. Past success of the tropical Atlantic observing system is the result of an international commitment to sustained observations and scientific cooperation, a willingness to evolve with changing research and monitoring needs, and a desire to share data openly with the scientific community and operational centers. The observing system must continue to evolve in order to meet an expanding set of research priorities and operational challenges. This paper discusses the tropical Atlantic observing system, including emerging scientific questions that demand sustained ocean observations, the potential for further integration of the observing system, and the requirements for sustaining and enhancing the tropical Atlantic observing system.

Evidences of organic acids exudation in aluminium stress responses of two Madeiran wheat (Triticum aestivum L.) landraces - Marta Rodrigues; José Filipe T. Ganança; Emanuel M. da Silva; Teresa M. M. dos Santos; Jan J. Slaski; Janusz Zimny; Miguel Â. A. Pinheiro de Carvalho (Genetic Resources and Crop Evolution, 2019)

Isolation by instability: Historical climate change shapes population structure and genomic divergence of treefrogs in the Neotropical Cerrado savanna - Mariana M. Vasconcellos; Guarino R. Colli; Jesse N. Weber; Edgardo M. Ortiz; Miguel T. Rodrigues; David C. Cannatella (Molecular Ecology, 2019)
Although the impact of Pleistocene glacial cycles on the diversification of the tropical biota was once dismissed, increasing evidence suggests that Pleistocene climatic fluctuations greatly affected the distribution and population divergence of tropical organisms. Landscape genomic analyses coupled with paleoclimatic distribution models provide a powerful way to understand the consequences of past climate changes on the present‐day tropical biota. Using genome‐wide SNP data and mitochondrial DNA, combined with projections of the species distribution across the late Quaternary until the present, we evaluate the effect of paleoclimatic shifts on the genetic structure and population differentiation of Hypsiboas lundii , a treefrog endemic to the South American Cerrado savanna. Our results show a recent and strong genetic divergence in H. lundii across the Cerrado landscape, yielding four genetic clusters that do not seem congruent with any current physical barrier to gene flow. Isolation by distance (IBD) explains some of the population differentiation, but we also find strong support for past climate changes promoting range shifts and structuring populations even in the presence of IBD. Post‐Pleistocene population persistence in four main areas of historical stable climate in the Cerrado seems to have played a major role establishing the present genetic structure of this treefrog. This pattern is consistent with a model of reduced gene flow in areas with high climatic instability promoting isolation of populations, defined here as “isolation by instability,” highlighting the effects of Pleistocene climatic fluctuations structuring populations in tropical savannas.

Correction to: Occurrence of anti-Leptospira spp. antibodies in Rhipidomys spp. from a forest fragment of the Brazilian Cerrado - D. O. Gomes; G. B. Ramos; V. B. A. Alves; A. Z. Ciuffa; L. P. Cuccato; T. F. M. dos Reis; A. M. C. Lima; M. G. Coelho; G. V. Tolesano-Pascoli; V. S. Rodrigues; M. P. J. Szabó; V. N. Ramos (Tropical Animal Health and Production, 2019)

Molecular phylogeny and hemipenial diversity of South American species of Amerotyphlops (Typhlopidae, Scolecophidia) - Roberta Graboski; Juan C. Arredondo; Felipe G. Grazziotin; Ariane A. A. da Silva; Ana L. C. Prudente; Miguel T. Rodrigues; Sandro L. Bonatto; Hussam Zaher (Zoologica Scripta, 2019)
Typhlopidae is the most diverse family of Scolecophidia, with 269 species. Amerotyphlops was recently erected within subfamily Typhlopinae and comprises fifteen species distributed from Mexico to Argentina and the southern Lesser Antilles. Despite recent advances, affinities among typhlopines remain poorly explored, and the phylogenetic relationships and morphology of the South American (SA) species were never accessed before. Here, we performed a phylogenetic analysis including 106 species of Typhlopidae and ten genes. Our dataset represents the most comprehensive for SA species, containing seven of eight recognized species. Corroborating previous studies, we recovered the main groups of Typhlopoidea, and for typhlopines, we recovered with strong support two clades: (a) the Greater Antilles radiation, and the (b) Lesser Antilles and SA radiation. Within the SA radiation, we recovered four main lineages: (a) a clade formed by A. tasymicris and A. minuisquamus ; (b) a clade composed by A. reticulatus as the sister group of all other SA species; (c) a clade composed by A. brongersmianus as the sister group of a clade comprising all Northeast Brazilian Species (NBS); and (d) a clade of the NBS, including A. yonenagae , A. arenensis , A. paucisquamus, and A. amoipira . We supplemented our phylogenetic result with the description of hemipenial morphology for seven SA species and comment their relevance to the systematics of Typhlopinae. Hemipenes of SA Amerotyphlops follow the general pattern in scolecophidians (single organ with undivided sulcus). Only A. reticulatus and A. minuisquamus have organs with calcified spines. According to our results, hemipenial ornamentation have shown highly informative and could represent a potential source of systematic and taxonomic characters in that group. We also present an extensive review of the geographical distribution for all SA species. Our study represents the first integrative analysis of a poorly known evolutionary radiation of one of the most widespread SA fossorial snakes.

Regulation of cell wall development in Brachypodium distachyon in vitro as affected by cytokinin and gas exchange - T. C. Mamedes-Rodrigues; D. S. Batista; T. A. Napoleão; E. A. Fortini; A. C. F. Cruz; M. G. C. Costa; W. C. Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Biofilm Formation by Avian Pathogenic Escherichia coli is Not Related to In Vivo Pathogenicity - Suelle V. Rodrigues; Vanessa Laviniki; Karen A. Borges; Thales Q. Furian; Hamilton L. S. Moraes; Vladimir P. Nascimento; Carlos T. P. Salle (Current Microbiology, 2019)

Toxicity of erythromycin to Oncorhynchus mykiss at different biochemical levels: detoxification metabolism, energetic balance, and neurological impairment - Sara Rodrigues; Sara C. Antunes; Alberto T. Correia; Bruno Nunes (Environmental Science and Pollution Research, 2019)

Crispoic acid, a new compound from Laelia marginata (Orchidaceae), and biological evaluations against parasites, human cancer cell lines and Zika virus - Andrezza C. Belloto; Gredson K. Souza; Paula C. Perin; Ivania T. A. Schuquel; Silvana M. O. Santin; Lucas U. R. Chiavelli; Francielle P. Garcia; Vanessa Kaplum; Jean H. S. Rodrigues; Débora B. Scariot; Rodrigo Delvecchio; Erik Machado-Ferreira; et al. (Natural Product Research, 2018)

Surviving in hot and cold: psychrophiles and thermophiles from Deception Island volcano, Antarctica - Amanda G. Bendia; Gabriel G. Araujo; André A. Pulschen; Bruna Contro; Rubens T. D. Duarte; Fábio Rodrigues; Douglas Galante; Vivian H. Pellizari (Extremophiles, 2018)

Phylogeography of Muller's termite frog suggests the vicariant role of the Central Brazilian Plateau - Eliana F. Oliveira; Marcelo Gehara; Vinícius A. São‐Pedro; Gabriel C. Costa; Frank T. Burbrink; Guarino R. Colli; Miguel T. Rodrigues; Adrian A. Garda (Journal of Biogeography, 2018)
Aim To test three different scenarios to account for the geographic distribution of genetic variation in Dermatonotus muelleri , a fossorial frog endemic of the South American diagonal of open formations ( DOF ) formed by Chaco, Cerrado, and Caatinga biomes: (a) The pan‐ DOF hypothesis, where these biomes behave as a single biogeographical unit and DOF species lack population structure; (b) the southwest‐northeast ( SW ‐ NE ) hypothesis, where structured populations along the DOF have either asymmetric or unidirectional gene flow in the northeast direction; (c) the vicariance hypothesis, where a pattern of population structure with no or reduced gene flow is observed. Location Caatinga, Cerrado, and Chaco in South America. Methods We sampled 179 individuals across the species distribution and sequenced one mitochondrial and two nuclear markers. We evaluated population structure, the presence, direction, and asymmetry of gene flow, and demographic changes to test three different phylogeographic hypotheses for D. muelleri using a model‐based simulation approach. Results We found two geographically structured lineages with no gene flow, refuting pan‐ DOF hypothesis. The Southwest lineage occurs in Chaco and western Cerrado and the Northeast lineage in eastern Cerrado and Caatinga. Our results support the model with demographic change for the Northeast lineage and constant size for Southwest lineage. The vicariance model with divergence time estimated around 4 Ma was preferred. Main conclusions Vicariance was the best explanation for the geographic distribution of genetic variation in Dermatonotus . Divergence time supports the role of Neogene orogeny in central Brazil for the splitting of Dermatonotus lineages. The influence of Pleistocene climatic fluctuations seems restricted to changes in one lineage's population size. Therefore, both ancient and recent events shaped the phylogeography of Dermatonotus . Genetic divergence, lack of gene flow, and the presence of a geographic barrier between lineages indicate the existence of a cryptic, undescribed species in northeastern Brazil.

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Origin and hidden diversity within the poorly known Galápagos snake radiation (Serpentes: Dipsadidae) - Hussam Zaher; Mario H. Yánez-Muñoz; Miguel T. Rodrigues; Roberta Graboski; Fabio A. Machado; Marco Altamirano-Benavides; Sandro L. Bonatto; Felipe G. Grazziotin (Systematics and Biodiversity, 2018)

A facile method to prepare translucent anatase thin films in monolithic structures for gas stream purification - Caio Rodrigues-Silva; Ricardo A. R. Monteiro; Márcia Dezotti; Adrián M. T. Silva; Eugénia Pinto; Rui A. R. Boaventura; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2018)

Histopathological Evaluation of Combined Impacts of the Synthetic Progestin Levonorgestrel and Temperature on the Female Zebrafish Maturation Using a Semi-quantitative Grading Analysis—Is it Enough? - P. G. Cardoso; D. Rodrigues; T. V. Madureira; M. J. Rocha; E. Rocha (Bulletin of Environmental Contamination and Toxicology, 2018)

The Híbrido de Timor germplasm: identification of molecular diversity and resistance sources to coffee berry disease and leaf rust - R. A. Silva; L. Zambolim; I. S. L. Castro; H. S. Rodrigues; C. D. Cruz; E. T. Caixeta (Euphytica, 2018)

Combined effects of insecticide exposure and predation risk on freshwater detritivores - Andreia C. M. Rodrigues; Maria D. Bordalo; Oksana Golovko; Olga Koba; Carlos Barata; Amadeu M. V. M. Soares; João L. T. Pestana (Ecotoxicology, 2018)

Nanoparticle vaccines against viral infections - Fernando B. Sulczewski; Raquel B. Liszbinski; Pedro R. T. Romão; Luiz Carlos Rodrigues Junior (Archives of Virology, 2018)

Mitochondrial genome analysis in penile carcinoma - L. F. Araujo; A. T. Terra; C. T. G. Sares; C. F. R. Sobreira; E. F. Faria; R. D. Machado; A. A. Rodrigues; V. F. Muglia; W. A. Silva; R. B. Reis (Molecular Biology Reports, 2018)

Publisher Correction to: Bacteria from Antarctic environments: diversity and detection of antimicrobial, antiproliferative, and antiparasitic activities - Tiago R. Silva; Alysson W. F. Duarte; Michel R. Z. Passarini; Ana Lucia T. G. Ruiz; Caio Haddad Franco; Carolina Borsoi Moraes; Itamar Soares de Melo; Rodney A. Rodrigues; Fabiana Fantinatti-Garboggini; Valéria Maia Oliveira (Polar Biology, 2018)

Bacteria from Antarctic environments: diversity and detection of antimicrobial, antiproliferative, and antiparasitic activities - Tiago R. Silva; Alysson W. F. Duarte; Michel R. Z. Passarini; Ana Lucia T. G. Ruiz; Caio Haddad Franco; Carolina Borsoi Moraes; Itamar Soares de Melo; Rodney A. Rodrigues; Fabiana Fantinatti-Garboggini; Valéria Maia Oliveira (Polar Biology, 2018)

Diversification with gene flow and niche divergence in a lizard species along the South American “diagonal of open formations” - Emanuel M. Fonseca; Marcelo Gehara; Fernanda P. Werneck; Flávia M. Lanna; Guarino R. Colli; Jack W. Sites; Miguel T. Rodrigues; Adrian A. Garda (Journal of Biogeography, 2018)
Aim To assess the effects of historical events on the tempo and mode of diversification of the lizard Polychrus acutirostris along the South American diagonal of open formations ( DOF ). Location Caatinga and Cerrado biomes in Brazil. Methods We sequenced fragments of one mt DNA and three nu DNA genes of 68 individuals from 33 localities. We used population assignment methods to access genetic structure and estimate lineage boundaries. Next, we estimated lineage relationships, intraspecific diversity, environmental niche similarity and demographic history. Finally, we tested 12 diversification scenarios using an approximate Bayesian computation ( ABC ) approach. Results We recovered three non‐overlapping, geographically structured lineages corresponding to Caatinga, north‐east Cerrado and south‐west Cerrado, with the major divergence event dating to the Late Neogene. We also recovered a complex scenario of divergence associated with gene flow and niche divergence. Main conclusions We show a complex history of diversification along the South American DOF . Our findings support the role of environmental features as the likely drivers of P. acutirostris intraspecific diversification during the Late Neogene.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Correction to: Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Diversity of endophytic fungi in Eucalyptus microcorys assessed by complementary isolation methods - Lorena T. Lacerda; Luís F. P. Gusmão; Andre Rodrigues (Mycological Progress, 2018)

Lignin and cellulose synthesis and antioxidative defense mechanisms are affected by light quality in Brachypodium distachyon - T. C. Mamedes-Rodrigues; D. S. Batista; T. A. Napoleão; A. C. F. Cruz; E. A. Fortini; F. T. S. Nogueira; E. Romanel; W. C. Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Usability of Computerized Lung Auscultation–Sound Software (CLASS) for learning pulmonary auscultation - Ana Machado; Ana Oliveira; Cristina Jácome; Marco Pereira; José Moreira; João Rodrigues; José Aparício; Luis M. T. Jesus; Alda Marques (Medical & Biological Engineering & Computing, 2018)

Regenerative potential, metabolic profile, and genetic stability of Brachypodium distachyon embryogenic calli as affected by successive subcultures - T. C. Mamedes-Rodrigues; D. S. Batista; N. M. Vieira; E. M. Matos; D. Fernandes; A. Nunes-Nesi; C. D. Cruz; L. F. Viccini; F. T. S. Nogueira; W. C. Otoni (Protoplasma, 2018)

Methionine Administration in Pregnant Rats Causes Memory Deficit in the Offspring and Alters Ultrastructure in Brain Tissue - Bruna Martins Schweinberger; André Felipe Rodrigues; Tiago Marcon dos Santos; Francieli Rohden; Silvia Barbosa; Paula Rigon da Luz Soster; Wania Aparecida Partata; Maria Cristina Faccioni-Heuser; Angela T. S. Wyse (Neurotoxicity Research, 2018)

Maternal Hypermethioninemia Affects Neurons Number, Neurotrophins Levels, Energy Metabolism, and Na+,K+-ATPase Expression/Content in Brain of Rat Offspring - Bruna M. Schweinberger; André F. Rodrigues; Elias Turcatel; Paula Pierozan; Leticia F. Pettenuzzo; Mateus Grings; Giselli Scaini; Mariana M. Parisi; Guilhian Leipnitz; Emilio L. Streck; Florencia M. Barbé-Tuana; Angela T. S. Wyse (Molecular Neurobiology, 2018)

Tingenone, a pentacyclic triterpene, induces peripheral antinociception due to cannabinoid receptors activation in mice - C. C. Veloso; R. C. M. Ferreira; V. G. Rodrigues; L. P. Duarte; A. Klein; I. D. Duarte; T. R. L. Romero; A. C. Perez (Inflammopharmacology, 2018)

Long-term effects of grazing and topography on extra-radical hyphae of arbuscular mycorrhizal fungi in semi-arid grasslands - Haiyan Ren; Weiyang Gui; Yongfei Bai; Claudia Stein; Jorge L. M. Rodrigues; Gail W. T. Wilson; Adam B. Cobb; Yingjun Zhang; Gaowen Yang (Mycorrhiza, 2018)

Methylphenidate Decreases ATP Levels and Impairs Glutamate Uptake and Na+,K+-ATPase Activity in Juvenile Rat Hippocampus - Felipe Schmitz; Paula Pierozan; André F. Rodrigues; Helena Biasibetti; Mateus Grings; Bruna Zanotto; Daniella M. Coelho; Carmen R. Vargas; Guilhian Leipnitz; Angela T. S. Wyse (Molecular Neurobiology, 2017)

Discovery of potential neurodegenerative inhibitors in Alzheimer’s disease by casein kinase 1 structure-based virtual screening - Ricardo P. Rodrigues; Carlos H. T. P. da Silva (Medicinal Chemistry Research, 2017)

New cytotoxic furan from the marine sediment-derived fungi Aspergillus niger - Paula Karina S. Uchoa; Antonia T. A. Pimenta; Raimundo Braz-Filho; Maria da Conceição F. de Oliveira; Natália N. Saraiva; Barbara S. F. Rodrigues; Ludwig H. Pfenning; Lucas M. Abreu; Diego V. Wilke; Katharine G. D. Florêncio; Mary Anne S. Lima (Natural Product Research, 2017)

Molecular phylogenetic diversity in the widespread lizard Cercosaura ocellata (Reptilia: Gymnophthalmidae) in South America - Marcelo José Sturaro; Teresa C. S. Avila-Pires; Miguel T. Rodrigues (Systematics and Biodiversity, 2017)

Physiological responses of reared sea bream ( Sparus aurata Linnaeus, 1758) to an Amyloodinium ocellatum outbreak - M Moreira; D Schrama; F Soares; T Wulff; P Pousão‐Ferreira; P Rodrigues (Journal of Fish Diseases, 2017)
Amyloodiniosis represents a major bottleneck for semi‐intensive aquaculture production in Southern Europe, causing extremely high mortalities. Amyloodinium ocellatum is a parasitic dinoflagellate that can infest almost all fish, crustacean and bivalves that live within its ecological range. Fish mortalities are usually attributed to anoxia, associated with serious gill hyperplasia, inflammation, haemorrhage and necrosis in heavy infestations; or with osmoregulatory impairment and secondary microbial infections due to severe epithelial damage in mild infestation. However, physiological information about the host responses to A. ocellatum infestation is scarce. In this work, we analysed the proteome of gilthead sea bream ( Sparus aurata ) plasma and relate it with haematological and immunological indicators, in order to enlighten the different physiological responses when exposed to an A. ocellatum outbreak. Using 2D‐ DIGE , immunological and haematological analysis and in response to the A. ocellatum contamination we have identified several proteins associated with acute‐phase response, inflammation, lipid transport, homoeostasis, and osmoregulation, wound healing, neoplasia and iron transport. Overall, this preliminary study revealed that amyloodiniosis affects some fish functional pathways as revealed by the changes in the plasma proteome of S. aurata, and that the innate immunological system is not activated in the presence of the parasite.

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Wax Removal and Diamondback Moth Performance in Collards Cultivars - G. A. Silva; R. M. Pereira; N. Rodrigues-Silva; T. C. Souza; D. O. Ferreira; E. A. Queiroz; G. A. R. Silva; M. C. Picanço (Neotropical Entomology, 2017)

Richness of periphytic algae and its relationship with hydrological attributes - Vanessa M. Algarte; Natália S. Siqueira; Daiane T. Ruwer; Nicolli C. Osório; Liliana Rodrigues (Brazilian Journal of Botany, 2017)

Evaluation of Oxidative Stress Parameters and Energy Metabolism in Cerebral Cortex of Rats Subjected to Sarcosine Administration - Rodrigo Binkowski de Andrade; Tanise Gemelli; Denise Bertin Rojas; Tomas Duk Hwa Kim; Ângela Zanatta; Felipe Schmitz; André Felipe Rodrigues; Angela T. S. Wyse; Moacir Wajner; Carlos Severo Dutra-Filho; Clovis Milton Duval Wannmacher (Molecular Neurobiology, 2017)

Methylphenidate Causes Behavioral Impairments and Neuron and Astrocyte Loss in the Hippocampus of Juvenile Rats - Felipe Schmitz; Paula Pierozan; André F. Rodrigues; Helena Biasibetti; Matheus Grunevald; Letícia F. Pettenuzzo; Giselli Scaini; Emilio L. Streck; Carlos A. Netto; Angela T. S. Wyse (Molecular Neurobiology, 2017)

Biology of the relict fungus-farming ant Apterostigma megacephala Lattke, including descriptions of the male, gyne, and larva - J. Sosa-Calvo; A. Ješovnik; C. T. Lopes; A. Rodrigues; C. Rabeling; M. Bacci; H. L. Vasconcelos; T. R. Schultz (Insectes Sociaux, 2017)

Global patterns of interaction specialization in bird–flower networks - Thais B. Zanata; Bo Dalsgaard; Fernando C. Passos; Peter A. Cotton; James J. Roper; Pietro K. Maruyama; Erich Fischer; Matthias Schleuning; Ana M. Martín González; Jeferson Vizentin‐Bugoni; Donald C. Franklin; Stefan Abrahamczyk; et al. (Journal of Biogeography, 2017)
Aim Among the world's three major nectar‐feeding bird taxa, hummingbirds are the most phenotypically specialized for nectarivory, followed by sunbirds, while the honeyeaters are the least phenotypically specialized taxa. We tested whether this phenotypic specialization gradient is also found in the interaction patterns with their floral resources. Location Americas, Africa, Asia and Oceania/Australia. Methods We compiled interaction networks between birds and floral resources for 79 hummingbird, nine sunbird and 33 honeyeater communities. Interaction specialization was quantified through connectance ( C ), complementary specialization ( H 2 ′), binary ( Q B ) and weighted modularity ( Q ), with both observed and null‐model corrected values. We compared interaction specialization among the three types of bird–flower communities, both independently and while controlling for potential confounding variables, such as plant species richness, asymmetry, latitude, insularity, topography, sampling methods and intensity. Results Hummingbird–flower networks were more specialized than honeyeater–flower networks. Specifically, hummingbird–flower networks had a lower proportion of realized interactions (lower C ), decreased niche overlap (greater H 2 ′) and greater modularity (greater Q B ). However, we found no significant differences between hummingbird– and sunbird–flower networks, nor between sunbird– and honeyeater–flower networks. Main conclusions As expected, hummingbirds and their floral resources have greater interaction specialization than honeyeaters, possibly because of greater phenotypic specialization and greater floral resource richness in the New World. Interaction specialization in sunbird–flower communities was similar to both hummingbird–flower and honeyeater–flower communities. This may either be due to the relatively small number of sunbird–flower networks available, or because sunbird–flower communities share features of both hummingbird–flower communities (specialized floral shapes) and honeyeater–flower communities (fewer floral resources). These results suggest a link between interaction specialization and both phenotypic specialization and floral resource richness within bird–flower communities at a global scale.

Hypoxanthine Intrastriatal Administration Alters Neuroinflammatory Profile and Redox Status in Striatum of Infant and Young Adult Rats - Helena Biasibetti; Paula Pierozan; André Felipe Rodrigues; Vanusa Manfredini; Angela T. S. Wyse (Molecular Neurobiology, 2017)

Occurrence of anti-Leptospira spp. antibodies in Rhipidomys spp. from a forest fragment of the Brazilian Cerrado - D. O. Gomes; G. B. Ramos; V. B. A. Alves; A. Z. Ciuffa; L. P. Cuccato; T. F. M. dos Reis; A. M. C. Lima; M. C. Gonçalves; G. V. Tolesano; V. S. Rodrigues; M. P. J. Szabó (Tropical Animal Health and Production, 2017)

Adaptative processes, control measures, genetic background, and resilience of malaria vectors and environmental changes in the Amazon region - W. P. Tadei; I. B. Rodrigues; M. S. Rafael; R. T. M. Sampaio; H. G. Mesquita; V. C. S. Pinheiro; J. A. C. Zequi; R. A. Roque; J. M. M. dos Santos (Hydrobiologia, 2017)

Bacteria and fungi inactivation by photocatalysis under UVA irradiation: liquid and gas phase - Caio Rodrigues-Silva; Sandra M. Miranda; Filipe V. S. Lopes; Mário Silva; Márcia Dezotti; Adrián M. T. Silva; Joaquim L. Faria; Rui A. R. Boaventura; Vítor J. P. Vilar; Eugénia Pinto (Environmental Science and Pollution Research, 2017)

Selection and Characterization of Bacillus thuringiensis (Berliner) (Eubacteriales: Bacillaceae) Strains for Ecdytolopha aurantiana (Lima) (Lepidoptera: Tortricidae) Control - J Zorzetti; A P S Ricietto; F A P Fazion; A M Meneguim; P M O J Neves; L A Vilas-Boas; R B Rodrigues; G T Vilas-Bôas (Neotropical Entomology, 2017)

Single-channel EEG sleep stage classification based on a streamlined set of statistical features in wavelet domain - Thiago L. T. da Silveira; Alice J. Kozakevicius; Cesar R. Rodrigues (Medical & Biological Engineering & Computing, 2017)

Elucidating constraints for differentiation of major human Klebsiella pneumoniae clones using MALDI-TOF MS - C. Rodrigues; Â. Novais; C. Sousa; H. Ramos; T. M. Coque; R. Cantón; J. A. Lopes; L. Peixe (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Climate change stimulates the growth of the intertidal macroalgae Ascophyllum nodosum near the northern distribution limit - Núria Marbà; Dorte Krause-Jensen; Birgit Olesen; Peter B. Christensen; Anissa Merzouk; Joao Rodrigues; Susse Wegeberg; Robert T. Wilce (Ambio, 2017)

Male spider mites use chemical cues, but not the female mating interval, to choose between mates - Leonor R. Rodrigues; Alexandre R. T. Figueiredo; Susana A. M. Varela; Isabelle Olivieri; Sara Magalhães (Experimental and Applied Acarology, 2017)

Bacterial host and reporter gene optimization for genetically encoded whole cell biosensors - Catherine Brutesco; Sandra Prévéral; Camille Escoffier; Elodie C. T. Descamps; Elsa Prudent; Julien Cayron; Louis Dumas; Manon Ricquebourg; Géraldine Adryanczyk-Perrier; Arjan de Groot; Daniel Garcia; Agnès Rodrigue; et al. (Environmental Science and Pollution Research, 2017)

Rainbow trout (Oncorhynchus mykiss) pro-oxidant and genotoxic responses following acute and chronic exposure to the antibiotic oxytetracycline - Sara Rodrigues; Sara C. Antunes; Alberto T. Correia; Bruno Nunes (Ecotoxicology, 2017)

Antarctic strict anaerobic microbiota from Deschampsia antarctica vascular plants rhizosphere reveals high ecology and biotechnology relevance - Rafael José Marques Peixoto; Karla Rodrigues Miranda; Leandro Araujo Lobo; Alessandra Granato; Pedro de Carvalho Maalouf; Hugo Emiliano de Jesus; Caio T. C. C. Rachid; Saulo Roni Moraes; Henrique Fragoso dos Santos; Raquel Silva Peixoto; Alexandre Soares Rosado; Regina Maria Cavalcanti Pilotto Domingues (Extremophiles, 2016)

Behavior of Atrazine and Its Degradation Products Deethylatrazine and Deisopropylatrazine in Oxisol Samples - Maristela F. Amadori; Marcio B. Rodrigues; Caio C. Rebouças; Patricio G. Peralta-Zamora; Marco T. Grassi; Gilberto Abate (Water, Air, & Soil Pollution, 2016)

A mid‐ P leistocene rainforest corridor enabled synchronous invasions of the A tlantic F orest by A mazonian anole lizards - Ivan Prates; Danielle Rivera; Miguel T. Rodrigues; Ana C. Carnaval (Molecular Ecology, 2016)
Shifts in the geographic distribution of habitats over time can promote dispersal and vicariance, thereby influencing large‐scale biogeographic patterns and ecological processes. An example is that of transient corridors of suitable habitat across disjunct but ecologically similar regions, which have been associated with climate change over time. Such connections likely played a role in the assembly of tropical communities, especially within the highly diverse Amazonian and Atlantic rainforests of South America. Although these forests are presently separated by open and dry ecosystems, paleoclimatic and phylogenetic evidence suggest that they have been transiently connected in the past. However, little is known about the timing, magnitude and the distribution of former forest connections. We employ sequence data at multiple loci from three codistributed arboreal lizards ( Anolis punctatus , Anolis ortonii and Polychrus marmoratus ) to infer the phylogenetic relationships among Amazonian and Atlantic Forest populations and to test alternative historical demographic scenarios of colonization and vicariance using coalescent simulations and approximate Bayesian computation ( ABC ). Data from the better‐sampled Anolis species support colonization of the Atlantic Forest from eastern Amazonia. Hierarchical ABC indicates that the three species colonized the Atlantic Forest synchronously during the mid‐Pleistocene. We find support of population bottlenecks associated with founder events in the two Anolis , but not in P. marmoratus , consistently with their distinct ecological tolerances. Our findings support that climatic fluctuations provided key opportunities for dispersal and forest colonization in eastern South America through the cessation of environmental barriers. Evidence of species‐specific histories strengthens assertions that biological attributes play a role in responses to shared environmental change.

Chronic Treatment with a Clinically Relevant Dose of Methylphenidate Increases Glutamate Levels in Cerebrospinal Fluid and Impairs Glutamatergic Homeostasis in Prefrontal Cortex of Juvenile Rats - Felipe Schmitz; Paula Pierozan; André F. Rodrigues; Helena Biasibetti; Daniella M. Coelho; Ben Hur Mussulini; Mery S. L. Pereira; Mariana M. Parisi; Florencia Barbé-Tuana; Diogo L. de Oliveira; Carmen R. Vargas; Angela T. S. Wyse (Molecular Neurobiology, 2016)

A novel N-acetyl-glucosamine lectin of Lonchocarpus araripensis attenuates acute cellular inflammation in mice - Alana F. Pires; Natália V. F. C. Rodrigues; Pedro Marcos G. Soares; Ronaldo de Albuquerque Ribeiro; Karoline S. Aragão; Márcia M. Marinho; Mayara T. L. da Silva; Benildo S. Cavada; Ana Maria S. Assreuy (Inflammation Research, 2016)

Speciation with gene flow in whiptail lizards from a Neotropical xeric biome - Eliana F. Oliveira; Marcelo Gehara; Vinícius A. São‐Pedro; Xin Chen; Edward A. Myers; Frank T. Burbrink; Daniel O. Mesquita; Adrian A. Garda; Guarino R. Colli; Miguel T. Rodrigues; Federico J. Arias; Hussam Zaher; et al. (Molecular Ecology, 2015)
Two main hypotheses have been proposed to explain the diversification of the Caatinga biota. The riverine barrier hypothesis ( RBH ) claims that the São Francisco River ( SFR ) is a major biogeographic barrier to gene flow. The Pleistocene climatic fluctuation hypothesis ( PCH ) states that gene flow, geographic genetic structure and demographic signatures on endemic Caatinga taxa were influenced by Quaternary climate fluctuation cycles. Herein, we analyse genetic diversity and structure, phylogeographic history, and diversification of a widespread Caatinga lizard ( Cnemidophorus ocellifer ) based on large geographical sampling for multiple loci to test the predictions derived from the RBH and PCH . We inferred two well‐delimited lineages (Northeast and Southwest) that have diverged along the Cerrado–Caatinga border during the Mid‐Late Miocene (6–14 Ma) despite the presence of gene flow. We reject both major hypotheses proposed to explain diversification in the Caatinga. Surprisingly, our results revealed a striking complex diversification pattern where the Northeast lineage originated as a founder effect from a few individuals located along the edge of the Southwest lineage that eventually expanded throughout the Caatinga. The Southwest lineage is more diverse, older and associated with the Cerrado–Caatinga boundaries. Finally, we suggest that C. ocellifer from the Caatinga is composed of two distinct species. Our data support speciation in the presence of gene flow and highlight the role of environmental gradients in the diversification process.

Erratum to: Species distribution and in vitro antifungal susceptibility profiles of yeast isolates from invasive infections during a Portuguese multicenter survey - I. Faria-Ramos; J. Neves-Maia; E. Ricardo; J. Santos-Antunes; A. T. Silva; S. Costa-de-Oliveira; E. Cantón; A. G. Rodrigues; C. Pina-Vaz (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Oxidative stress markers in fish (Astyanax sp. and Danio rerio) exposed to urban and agricultural effluents in the Brazilian Pampa biome - D. G. Costa-Silva; M. E. M Nunes; G. L. Wallau; I. K. Martins; A. P. P Zemolin; L. C. Cruz; N. R. Rodrigues; A. R. Lopes; T. Posser; J. L. Franco (Environmental Science and Pollution Research, 2015)

Disease alters macroecological patterns of N orth A merican bats - Winifred F. Frick; Sébastien J. Puechmaille; Joseph R. Hoyt; Barry A. Nickel; Kate E. Langwig; Jeffrey T. Foster; Kate E. Barlow; Tomáš Bartonička; Dan Feller; Anne‐Jifke Haarsma; Carl Herzog; Ivan Horáček; et al. (Global Ecology and Biogeography, 2015)
Aim We investigated the effects of disease on the local abundances and distributions of species at continental scales by examining the impacts of white‐nose syndrome, an infectious disease of hibernating bats, which has recently emerged in N orth A merica. Location N orth A merica and E urope. Methods We used four decades of population counts from 1108 populations to compare the local abundances of bats in N orth A merica before and after the emergence of white‐nose syndrome to the situation in E urope, where the disease is endemic. We also examined the probability of local extinction for six species of hibernating bats in eastern N orth A merica and assessed the influence of winter colony size prior to the emergence of white‐nose syndrome on the risk of local extinction. Results White‐nose syndrome has caused a 10‐fold decrease in the abundance of bats at hibernacula in N orth A merica, eliminating large differences in species abundance patterns that existed between E urope and N orth A merica prior to disease emergence. White‐nose syndrome has also caused extensive local extinctions (up to 69% of sites in a single species). For five out of six species, the risk of local extinction was lower in larger winter populations, as expected from theory, but for the most affected species, the northern long‐eared bat ( M yotis septentrionalis ), extinction risk was constant across winter colony sizes, demonstrating that disease can sometimes eliminate numerical rarity as the dominant driver of extinction risk by driving both small and large populations extinct. Main conclusions Species interactions, including disease, play an underappreciated role in macroecological patterns and influence broad patterns of species abundance, occurrence and extinction.

The effect of conventional mechanical periodontal treatment on red complex microorganisms and clinical parameters in Down syndrome periodontitis patients: a pilot study - M. H. Tanaka; T. O. Rodrigues; L. S. Finoti; S. R. L. Teixeira; M. P. A. Mayer; R. M. Scarel-Caminaga; E. M. A. Giro (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Primary Productivity Temporal Fluctuations in a Nutrient-Rich Estuary due to Climate-Driven Events - Elsa T. Rodrigues; Miguel Â. Pardal (Estuaries and Coasts, 2015)

Solar photocatalytic gas-phase degradation of n-decane—a comparative study using cellulose acetate monoliths coated with P25 or sol-gel TiO2 films - Sandra M. Miranda; Filipe V. S. Lopes; Caio Rodrigues-Silva; Susana D. S. Martins; Adrián M. T. Silva; Joaquim L. Faria; Rui A. R. Boaventura; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2015)

Novel isomannide-based peptide mimetics containing a tartaric acid backbone as serine protease inhibitors - Bárbara Abrahim-Vieira; Emmerson C. B. da Costa; Pedro H. R. de A. Azevedo; Aline C. Portela; Luiza R. S. Dias; Sergio Pinheiro; Amilcar Tanuri; Anne M. Capaccia; Gustavo T. Ventura; Ronaldo Mohana-Borges; Carlos R. Rodrigues; Alessandra M. T. de Souza; et al. (Medicinal Chemistry Research, 2014)

Species distribution and in vitro antifungal susceptibility profiles of yeast isolates from invasive infections during a Portuguese multicenter survey - I. Faria-Ramos; J. Neves-Maia; E. Ricardo; J. Santos-Antunes; A. T. Silva; S. Costa-de-Oliveira; E. Cantón; A. G. Rodrigues; C. Pina-Vaz (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Bacterial diversity assessment in soil of an active Brazilian copper mine using high-throughput sequencing of 16S rDNA amplicons - Viviane D. Rodrigues; Tatiana T. Torres; Laura M. M. Ottoboni (Antonie van Leeuwenhoek, 2014)

Exploring N-Acylhydrazone Derivatives Against Clinical Resistant Bacterial Strains - Andressa C. Lannes; Bruno Leal; Juliana S. Novais; Viviane Lione; Georgia C. T. S. Monteiro; André L. Lourenço; Plínio C. Sathler; Alessandro K. Jordão; Carlos R. Rodrigues; Lúcio M. Cabral; Anna Claudia Cunha; Vinicius Campos; et al. (Current Microbiology, 2014)

Description of a strain from an atypical population of Aspergillus parasiticus that produces aflatoxins B only, and the impact of temperature on fungal growth and mycotoxin production - Arita C; Calado T; Venâncio A; Lima N; Rodrigues P (European Journal of Plant Pathology, 2014)

Early postnatal, but not late, exposure to chemical ambient pollutant 1,2-naphthoquinone increases susceptibility to pulmonary allergic inflammation at adulthood - Karen T. Santos; Juliana Florenzano; Leandro Rodrigues; Rodolfo R. Fávaro; Fernanda F. Ventura; Marcela G. Ribeiro; Simone A. Teixeira; Heloisa H. A. Ferreira; Susan D. Brain; Amílcar S. Damazo; Telma M. Zorn; Niels O. Câmara; et al. (Archives of Toxicology, 2014)

Mercury Bioaccumulation in the Egyptian Mongoose (Herpestes ichneumon): Geographical, Tissue, Gender and Age Differences - S. Rodrigues; J. P. Coelho; V. Bandeira; T. Barros; A. C. Duarte; C. Fonseca; M. E. Pereira (Water, Air, & Soil Pollution, 2014)

Stability, genotypic and phenotypic diversity of S hewanella baltica in the redox transition zone of the B altic S ea - Jie Deng; Ingrid Brettar; Chengwei Luo; Jennifer Auchtung; Konstantinos T. Konstantinidis; Jorge L. M. Rodrigues; Manfred Höfle; James M. Tiedje (Environmental Microbiology, 2014)
Summary Studying how bacterial strains diverge over space and time and how divergence leads to ecotype formation is important for understanding structure and dynamics of environmental communities. Here we assess the ecological speciation and temporal dynamics of a collection of S hewanella baltica strains from the redox transition zone of the central B altic Sea, sampled at three time points over a course of 12 years, with a subcollection containing 46 strains subjected to detailed genetic and physiological characterization. Nine clades were consistently recovered by three different genotyping approaches: gyrB gene sequencing, multilocus sequence typing ( MLST ) and whole genome clustering of data from comparative genomic hybridization, and indicated specialization according to nutrient availability, particle association and temporal distribution. Genomic analysis suggested higher intra‐ than inter‐clade recombination that might result from niche partitioning. Substantial heterogeneity in carbon utilization and respiratory capabilities suggested rapid diversification within the same ‘named’ species and physical habitat and showed consistency with genetic relatedness. At least two major ecotypes, represented by MLST clades A and E , were proposed based on genetic, ecological and physiological distinctiveness. This study suggests that genetic analysis in conjunction with phenotypic evaluation can provide better understanding of the ecological framework and evolutionary trajectories of microbial species.

Light and temperature induce variations in the density and ultrastructure of the secretory spaces in the diesel-tree (Copaifera langsdorffii Desf.—Leguminosae) - T. M. Rodrigues; P. F. S. M. Buarque; A. G. Coneglian; D. C. Reis (Trees, 2014)

Effects of a commercial extract of the brown alga Ascophyllum nodosum on the biomass production of Kappaphycus alvarezii (Doty) Doty ex P. C. Silva and its carrageenan yield and gel quality cultivated in Brazil - Rafael Rodrigues Loureiro; Renata Perpetuo Reis; Flávia Diniz Berrogain; Alan T. Critchley (Journal of Applied Phycology, 2014)

Tuned liquid dampers simulation for earthquake response control of buildings - T. Novo; H. Varum; F. Teixeira-Dias; H. Rodrigues; M. Falcao Silva; A. Campos Costa; L. Guerreiro (Bulletin of Earthquake Engineering, 2014)

Purification and biochemical characterization of glucose–cellobiose-tolerant cellulases from Scytalidium thermophilum - Jean Carlos Rodrigues Silva; Luis Henrique Souza Guimarães; José Carlos Santos Salgado; Rosa Prazeres Melo Furriel; Maria Lourdes T. M. Polizeli; José César Rosa; João Atilio Jorge (Folia Microbiologica, 2013)

Mercury Toxicity to Freshwater Organisms: Extrapolation Using Species Sensitivity Distribution - Andreia C. M. Rodrigues; Fátima T. Jesus; Marco A. F. Fernandes; Fernando Morgado; Amadeu M. V. M. Soares; Sizenando N. Abreu (Bulletin of Environmental Contamination and Toxicology, 2013)

Characterization of water and wildlife strains as a subgroup of C ampylobacter jejuni using DNA microarrays - Richard A. Stabler; Jonas T. Larsson; Suaad Al‐Jaberi; Eva M. Nielsen; Emily Kay; Clarence C. Tam; Craig D. Higgins; Laura C. Rodrigues; Judith F. Richardson; Sarah J. O'Brien; Brendan W. Wren (Environmental Microbiology, 2013)
Summary C ampylobacter jejuni is the leading cause of human bacterial gastroenteritis worldwide, but source attribution of the organism is difficult. Previously, DNA microarrays were used to investigate isolate source, which suggested a non‐livestock source of infection. In this study we analysed the genome content of 162 clinical, livestock and water and wildlife ( WW ) associated isolates combined with the previous study. Isolates were grouped by genotypes into nine clusters ( C 1 to C 9). Multilocus sequence typing ( MLST ) data demonstrated that livestock associated clonal complexes dominated clusters C 1– C 6. The majority of WW isolates were present in the C 9 cluster. Analysis of previously reported genomic variable regions demonstrated that these regions were linked to specific clusters. Two novel variable regions were identified. A six gene multiplex PCR ( mPCR ) assay, designed to effectively differentiated strains into clusters, was validated with 30 isolates. A further five WW isolates were tested by m PCR and were assigned to the C 7‐ C 9 group of clusters. The predictive mPCR test could be used to indicate if a clinical case has come from domesticated or WW sources. Our findings provide further evidence that WW C . jejuni subtypes show niche adaptation and may be important in causing human infection.

Systematics of spiny‐backed treefrogs ( H ylidae: O steocephalus ): an A mazonian puzzle - Karl‐Heinz Jungfer; Julián Faivovich; José M. Padial; Santiago Castroviejo‐Fisher; Mariana M. Lyra; Bianca V. M. Berneck; Patricia P. Iglesias; Philippe J. R. Kok; Ross D. MacCulloch; Miguel T. Rodrigues; Vanessa K. Verdade; Claudia P. Torres Gastello; et al. (Zoologica Scripta, 2013)
Spiny‐backed tree frogs of the genus O steocephalus are conspicuous components of the tropical wet forests of the A mazon and the G uiana S hield. Here, we revise the phylogenetic relationships of O steocephalus and its sister group T epuihyla , using up to 6134 bp of DNA sequences of nine mitochondrial and one nuclear gene for 338 specimens from eight countries and 218 localities, representing 89% of the 28 currently recognized nominal species. Our phylogenetic analyses reveal (i) the paraphyly of O steocephalus with respect to T epuihyla , (ii) the placement of ‘ H yla’ warreni as sister to T epuihyla , (iii) the non‐monophyly of several currently recognized species within O steocephalus and (iv) the presence of low ( O . taurinus and O . oophagus ) for the 16 S gene fragment used in amphibian DNA barcoding. We propose a new taxonomy, securing the monophyly of O steocephalus and T epuihyla by rearranging and redefining the content of both genera and also erect a new genus for the sister group of O steocephalus . The colouration of newly metamorphosed individuals is proposed as a morphological synapomorphy for O steocephalus . We recognize and define five monophyletic species groups within O steocephalus , synonymize three species of O steocephalus ( O . germani , O . phasmatus and O . vilmae ) and three species of T epuihyla ( T . celsae , T . galani and T . talbergae ) and reallocate three species ( H yla helenae to O steocephalus , O . exophthalmus to T epuihyla and O . pearsoni to D ryaderces gen. n.). Furthermore, we flag nine putative new species (an increase to 138% of the current diversity). We conclude that species numbers are largely underestimated, with most hidden diversity centred on widespread and polymorphic nominal species. The evolutionary origin of breeding strategies within O steocephalus is discussed in the light of this new phylogenetic hypothesis, and a novel type of amplexus (gular amplexus) is described.

Presence of Torque Teno Virus (TTV) in Tap Water in Public Schools from Southern Brazil - Andréia Dalla Vecchia; Mariana Kluge; Joseane V. dos Santos da Silva; Juliana Comerlato; Manoela T. Rodrigues; Juliane D. Fleck; Roger B. da Luz; Thais F. Teixeira; Paulo M. Roehe; Roberta Capalonga; Ana Beatriz Oliveira; Fernando R. Spilki (Food and Environmental Virology, 2013)

Landslide hazard and cascading effects following the extreme rainfall event on Madeira Island (February 2010) - Hieu T. Nguyen; Thomas Wiatr; Tómas M. Fernández-Steeger; Klaus Reicherter; Domingos M. M. Rodrigues; Rafig Azzam (Natural Hazards, 2013)

First record of a whale shark Rhincodon typus in continental Europe - N. V. Rodrigues; J. P. S. Correia; J. T. C. Graça; F. Rodrigues; R. Pinho; M. Hirofumi (Journal of Fish Biology, 2012)
A whale shark Rhincodon typus was found in a set‐net in southern Portugal in October 2011. This was the first record for continental Europe and represents an increase of the species' known range. Upwelling events and increase in sea‐surface temperatures are possible reasons for this occurrence.

Unravelling Secretion in Cryptococcus neoformans: More than One Way to Skin a Cat - Marcio L. Rodrigues; Julianne T. Djordjevic (Mycopathologia, 2012)

Extract powder from the brown alga Ascophyllum nodosum (Linnaeus) Le Jolis (AMPEP): a “vaccine-like” effect on Kappaphycus alvarezii (Doty) Doty ex P.C. Silva - Rafael Rodrigues Loureiro; Renata Perpetuo Reis; Flávia Diniz Berrogain; Alan T. Critchley (Journal of Applied Phycology, 2012)

BMPRIB and BMPRII mRNA expression levels in goat ovarian follicles and the in vitro effects of BMP-15 on preantral follicle development - Isadora Machado T. Lima; Ivina R. Brito; Rafael Rossetto; Ana Beatriz G. Duarte; Giovanna Q. Rodrigues; Márcia Viviane A. Saraiva; José Jackson N. Costa; Mariana Aragão M. Donato; Christina A. Peixoto; José Roberto V. Silva; José Ricardo de Figueiredo; Ana Paula R. Rodrigues (Cell and Tissue Research, 2012)

The dual crop coefficient approach using a density factor to simulate the evapotranspiration of a peach orchard: SIMDualKc model versus eddy covariance measurements - T. A. Paço; M. I. Ferreira; R. D. Rosa; P. Paredes; G. C. Rodrigues; N. Conceição; C. A. Pacheco; L. S. Pereira (Irrigation Science, 2012)

Effect of pH and Temperature on Enzyme Activity of Chitosanase Produced Under Solid Stated Fermentation by Trichoderma spp. - Luis C. A. da Silva; Talita L. Honorato; Rosane S. Cavalcante; Telma T. Franco; Sueli Rodrigues (Indian Journal of Microbiology, 2012)

Hg transfer from contaminated soils to plants and animals - S. M. Rodrigues; B. Henriques; A. T. Reis; A. C. Duarte; E. Pereira; P. F. A. M. Römkens (Environmental Chemistry Letters, 2012)

Heavy Metals Contamination in Century-Old Manmade Technosols of Hope Bay, Antarctic Peninsula - Marcelo Braga Bueno Guerra; Carlos Ernesto G. R. Schaefer; Paula de Freitas Rosa; Felipe N. B. Simas; Thiago T. C. Pereira; Edenir Rodrigues Pereira-Filho (Water, Air, & Soil Pollution, 2011)

Vascular endothelial growth factor-A165 (VEGF-A165) stimulates the in vitro development and oocyte competence of goat preantral follicles - V. R. Araújo; G. M. Silva; A. B. G. Duarte; D. M. Magalhães; A. P. Almeida; R. F. B. Gonçalves; J. B. Bruno; T. F. P. Silva; C. C. Campello; A. P. R. Rodrigues; J. R. Figueiredo (Cell and Tissue Research, 2011)

Application of flow cytometry for the identification of Staphylococcus epidermidis by peptide nucleic acid fluorescence in situ hybridization (PNA FISH) in blood samples - N. F. Azevedo; T. Jardim; C. Almeida; L. Cerqueira; A. J. Almeida; F. Rodrigues; C. W. Keevil; M. J. Vieira (Antonie van Leeuwenhoek, 2011)

Oxoquinoline Derivatives: Identification and Structure–Activity Relationship (SAR) Analysis of New Anti-HSV-1 Agents - Paula A. Abreu; Viveca A. G. G. da Silva; Fernanda C. Santos; Helena C. Castro; Cecília S. Riscado; Mariana T. de Souza; Camilly P. Ribeiro; Juliana E. Barbosa; Cláudio C. C. dos Santos; Carlos R. Rodrigues; Viviane Lione; Bianca A. M. Correa; et al. (Current Microbiology, 2011)

Unraveling new genes associated with seed development and metabolism in Bixa orellana L. by expressed sequence tag (EST) analysis - Virgínia L. F. Soares; Simone M. Rodrigues; Tahise M. de Oliveira; Talisson O. de Queiroz; Lívia S. Lima; Braz T. Hora-Júnior; Karina P. Gramacho; Fabienne Micheli; Júlio C. M. Cascardo; Wagner C. Otoni; Abelmon S. Gesteira; Marcio G. C. Costa (Molecular Biology Reports, 2011)

Identification of Nor-β-Lapachone Derivatives as Potential Antibacterial Compounds against Enterococcus faecalis Clinical Strain - André L. Lourenço; Paula A. Abreu; Bruno Leal; Eufrânio N. da Silva Júnior; Antonio V. Pinto; Maria do Carmo F. R. Pinto; Alessandra M. T. Souza; Juliana S. Novais; Marcela B. Paiva; Lucio M. Cabral; Carlos R. Rodrigues; Vitor F. Ferreira; et al. (Current Microbiology, 2011)

Estimating parameters of a forest ecosystem C model with measurements of stocks and fluxes as joint constraints - Andrew D. Richardson; Mathew Williams; David Y. Hollinger; David J. P. Moore; D. Bryan Dail; Eric A. Davidson; Neal A. Scott; Robert S. Evans; Holly Hughes; John T. Lee; Charles Rodrigues; Kathleen Savage (Oecologia, 2010)

Seroprevalence of orthopoxvirus in an Amazonian rural village, Acre, Brazil - B. E. F. Mota; G. S. Trindade; T. C. Diniz; M. da Silva-Nunes; E. M. Braga; M. Urbano-Ferreira; G. O. L. Rodrigues; C. A. Bonjardim; P. C. P. Ferreira; E. G. Kroon (Archives of Virology, 2010)

Using taxonomically unbiased criteria to prioritize resource allocation for oceanic island species conservation - José L. Martín; Pedro Cardoso; Manuel Arechavaleta; Paulo A. V. Borges; Bernardo F. Faria; Cristina Abreu; António F. Aguiar; José A. Carvalho; Ana C. Costa; Regina T. Cunha; Francisco M. Fernandes; Rosalina Gabriel; et al. (Biodiversity and Conservation, 2010)

In vitro cultivation of three Kappaphycus alvarezii (Rhodophyta, Areschougiaceae) variants (green, red and brown) exposed to a commercial extract of the brown alga Ascophyllum nodosum (Fucaceae, Ochrophyta) - Rafael Rodrigues Loureiro; Renata Perpetuo Reis; Alan T. Critchley (Journal of Applied Phycology, 2010)

The potential ecological costs and cobenefits of REDD: a critical review and case study from the Amazon region - CLAUDIA M. STICKLER; DANIEL C. NEPSTAD; MICHAEL T. COE; DAVID G. McGRATH; HERMANN O. RODRIGUES; WAYNE S. WALKER; BRITALDO S. SOARES‐FILHO; ERIC A. DAVIDSON (Global Change Biology, 2009)
The United Nations climate treaty may soon include a mechanism for compensating tropical nations that succeed in reducing carbon emissions from deforestation and forest degradation, source of nearly one fifth of global carbon emissions. We review the potential for this mechanism [reducing emissions from deforestation and degradation (REDD)] to provoke ecological damages and promote ecological cobenefits. Nations could potentially participate in REDD by slowing clear‐cutting of mature tropical forest, slowing or decreasing the impact of selective logging, promoting forest regeneration and restoration, and expanding tree plantations. REDD could also foster efforts to reduce the incidence of forest fire. Potential ecological costs include the accelerated loss (through displaced agricultural expansion) of low‐biomass, high‐conservation‐value ecosystems, and substitution of low‐biomass vegetation by monoculture tree plantations. These costs could be avoided through measures that protect low‐biomass native ecosystems. Substantial ecological cobenefits should be conferred under most circumstances, and include the maintenance or restoration of (1) watershed functions, (2) local and regional climate regimes, (3) soils and biogeochemical processes, (4) water quality and aquatic habitat, and (5) terrestrial habitat. Some tools already being developed to monitor, report and verify (MRV) carbon emissions performance can also be used to measure other elements of ecosystem function, making development of MRV systems for ecological cobenefits a concrete possibility. Analysis of possible REDD program interventions in a large‐scale Amazon landscape indicates that even modest flows of forest carbon funding can provide substantial cobenefits for aquatic ecosystems, but that the functional integrity of the landscape's myriad small watersheds would be best protected under a more even spatial distribution of forests. Because of its focus on an ecosystem service with global benefits, REDD could access a large pool of global stakeholders willing to pay to maintain carbon in forests, thereby providing a potential cascade of ecosystem services to local stakeholders who would otherwise be unable to afford them.

Overexpression of the Arabidopsis anaphase promoting complex subunit CDC27a increases growth rate and organ size - Cristian Antonio Rojas; Nubia Barbosa Eloy; Marcelo de Freitas Lima; Roberta Lopes Rodrigues; Luciana Ozório Franco; Kristiina Himanen; Gerrit T. S. Beemster; Adriana Silva Hemerly; Paulo Cavalcanti Gomes Ferreira (Plant Molecular Biology, 2009)

Effect of Batch and Fed-Batch Growth Modes on Biofilm Formation by Listeria monocytogenes at Different Temperatures - Diana A. Rodrigues; Marta A. Almeida; Pilar A. Teixeira; Rosário T. Oliveira; Joana C. Azeredo (Current Microbiology, 2009)

Leishmania amazonensis Growth Inhibitors: Biological and Theoretical Features of Sulfonamide 4-Methoxychalcone Derivatives - Alessandra M. T. Souza; Helena C. Castro; Monique A. Brito; Carla R. Andrighetti-Fröhner; Uiaran Magalhães; Kely N. Oliveira; Daniela Gaspar-Silva; Letícia K. Pacheco; Antônio C. Joussef; Mário Steindel; Cláudia M. O. Simões; Dilvani O. Santos; et al. (Current Microbiology, 2009)

Assessment of high-level gentamicin and glycopeptide-resistant Enterococcus faecalis and E. faecium clonal structure in a Portuguese hospital over a 3-year period - R. Mato; F. Almeida; R. Pires; P. Rodrigues; T. Ferreira; I. Santos-Sanches (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

A role for atorvastatin and insulin combination in protecting from liver injury in a model of type 2 diabetes with hyperlipidemia - P. Matafome; E. Nunes; T. Louro; C. Amaral; J. Crisóstomo; L. Rodrigues; A. R. Moedas; P. Monteiro; A. Cipriano; R. Seiça (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Relevance of bacterioplankton abundance and production in the oligotrophic equatorial Indian Ocean - Veronica Fernandes; Veera Rodrigues; N. Ramaiah; Jane T. Paul (Aquatic Ecology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Spatial heterogeneity recognition in estuarine intertidal benthic macrofaunal communities: influence of sieve mesh-size and sampling depth - Ana Maria Rodrigues; S. Meireles; T. Pereira; V. Quintino (Hydrobiologia, 2007)

Water tank and numerical model studies of flow over steep smooth two-dimensional hills - J. B. R. Loureiro; D. V. Soares; J. L. A. Fontoura Rodrigues; F. T. Pinho; A. P. Silva Freire (Boundary-Layer Meteorology, 2007)

The effects of fructose-1,6-bisphosphate and dexamethasone on acute inflammation and T-cell proliferation - R. Pestana Lopes; A. Lunardelli; T. Preissler; C. E. Leite; J. C. F. Alves-Filho; F. Bordignon Nunes; J. Rodrigues de Oliveira; M. E. Bauer (Inflammation Research, 2006)

Anti-inflammatory properties of kefir and its polysaccharide extract - K. L. Rodrigues; J. C. T. Carvalho; J. M. Schneedorf (Inflammopharmacology, 2005)

Endosperm-preferred Expression of Maize Genes as Revealed by Transcriptome-wide Analysis of Expressed Sequence Tags - Natalia C. Verza; Thaís Rezende e Silva; Germano Cord Neto; Fábio T. S. Nogueira; Paulo H. Fisch; Vincente E. de Rosa; Marcelo M. Rebello; André L. Vettore; Felipe Rodrigues da Silva; Paulo Arruda (Plant Molecular Biology, 2005)

Meiotic instability of chicken ultra-long telomeres and mapping of a 2.8 megabase array to the W-sex chromosome - K. L. Rodrigue; B. P. May; T. R. Famula; M. E. Delany (Chromosome Research, 2005)

Larval Cryptothelea gloverii (Lepidoptera: Psycidae), an arthropod predator and herbivore on Florida citrus - Raul T. Villanueva; Jose C. V. Rodrigues; Carl C. Childers (Experimental and Applied Acarology, 2005)

Inorganic chemical composition of native trees of the Atlantic Forest - E. J. França; E. A. De Nadai Fernandes; M. A. Bacchi; R. R. Rodrigues; T. G. Verburg (Environmental Monitoring and Assessment, 2005)

Spatial and temporal variability in forest–atmosphere CO 2 exchange - D. Y. Hollinger; J. Aber; B. Dail; E. A. Davidson; S. M. Goltz; H. Hughes; M. Y. Leclerc; J. T. Lee; A. D. Richardson; C. Rodrigues; N.A. Scott; D. Achuatavarier; et al. (Global Change Biology, 2004)
Seven years of carbon dioxide flux measurements indicate that a ∼90‐year‐old spruce dominated forest in Maine, USA, has been sequestering 174±46 g C m −2 yr −1 (mean±1 standard deviation, nocturnal friction velocity ( u * ) threshold >0.25 m s −1 ). An analysis of monthly flux anomalies showed that above‐average spring and fall temperatures were significantly correlated with greater monthly C uptake while above‐average summer temperatures were correlated with decreased net C uptake. Summer months with significantly drier or wetter soils than normal were also characterized by lower rates of C uptake. Years with above‐average C storage were thus typically characterized by warmer than average spring and fall temperatures and adequate summer soil moisture. Environmental and forest–atmosphere flux data recorded from a second tower surrounded by similar forest, but sufficiently distant that flux source regions (‘footprints’), did not overlap significantly showed almost identical temperature and solar radiation conditions, but some differences in energy partitioning could be seen. Half‐hourly as well as integrated (annual) C exchange values recorded at the separate towers were very similar, with average annual net C uptake differing between the two towers by

Changes in Carbon Storage and Net Carbon Exchange One Year After an Initial Shelterwood Harvest at Howland Forest, ME - Neal A. Scott; Charles A. Rodrigues; Holly Hughes; John T. Lee; Eric A. Davidson; D. Bryan Dail; Phil Malerba; David Y. Hollinger (Environmental Management, 2004)

Phase Transition of Thylakoid Membranes Modulates Photoinhibition in the Cyanobacterium Anabaena siamensis - Ricardo M. Chaloub; Luiz Mauro T. Silva; Marcoaurélio A. Rodrigues; Cesar P. Dos Santos (Photosynthesis Research, 2003)

Hard X-ray microprobe studies of chromium(VI)-treated V79 Chinese hamster lung cells: intracellular mapping of the biotransformation products of a chromium carcinogen - Carolyn T. Dillon; Peter A. Lay; Brendan J. Kennedy; Anton P. Stampfl; Zhonghou Cai; Peter Ilinski; William Rodrigues; Daniel G. Legnini; Barry Lai; Jörg Maser (JBIC Journal of Biological Inorganic Chemistry, 2002)

Microbiology and physiology of Cachaça (Aguardente) fermentations - Rosane Freitas Schwan; Alexandre T. Mendonça; João José da Silva; Valéria Rodrigues; Alan E. Wheals (Antonie van Leeuwenhoek, 2001)

Varying responses of herbivorous and invertebrate-feeding fishes to macroalgal reduction on a coral reef - T. R. McClanahan; V. Hendrick; M. J. Rodrigues; N. V. C. Polunin (Coral Reefs, 1999)

Sediment chemistry — Infaunal community structure in a southern European estuary related to solid-phase Microtox® toxicity testing - V. Quintino; A. M. Picado; A. M. Rodrigues; E. Mendonça; M. H. Costa; M. Bordalo Costa; P. Lindgaard-Jørgensen; T. H. Pearson (Aquatic Ecology, 1995)

Pichia humboldtii sp. nov., the perfect state of Candida ingens - L. Rodrigues de Miranda; T. Trk (Antonie van Leeuwenhoek, 1976)